Disassembly method and adhesive sheet

By using acrylic polymer adhesive sheets and low-alcohol stripping solutions, the problem of disassembling components with low hydrophilicity is solved, achieving a balance between bonding reliability and ease of disassembly, and reducing the force required for disassembly operations and the risk of component damage.

CN122319213APending Publication Date: 2026-06-30NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480076796.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-04
Filing Date
2024-11-19
Publication Date
2026-06-30

AI Technical Summary

Technical Problem

Existing technologies struggle to simultaneously achieve reliable bonding and easy disassembly for components with low hydrophilicity, especially when disassembling adhesive-bonded components, which often presents challenges such as disassembly difficulties or component damage.

Method used

An adhesive sheet containing acrylic polymers as the base polymer is used to disintegrate the bond by immersing it in a release solution mainly composed of low alcohols with 1 to 5 carbon atoms, thereby reducing the adhesive force.

Benefits of technology

It enables efficient disassembly of components with low hydrophilicity, maintains reliable joints, exhibits good durability in alcoholic liquids, reduces the force required for disassembly operations, and minimizes the risk of component damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122319213A_ABST
    Figure CN122319213A_ABST
Patent Text Reader

Abstract

A method for disassembling a joint that can also be applied to the disassembly of joints containing components with low hydrophilicity, and simultaneously achieves both joint reliability and ease of disassembly, is provided. The method includes an adhesive sheet having a first adhesive surface and a first component bonded to the first adhesive surface. The method comprises: immersing the joint in a peeling solution primarily composed of a low alcohol having 1 to 5 carbon atoms; and disassembling the joint after immersion. In a peel test conducted using a stainless steel sheet as the adherend, the reduction rate R of the ethanol peel force N1 [N / 20mm] relative to the typical peel force N0 [N / 20mm] at the first measurement of the adhesive sheet is... A The percentage is over 70%, and the average peel force N0 in the second measurement is relative to the average peel force N0 [N / 20mm] in the first measurement. S [N / 20mm] reduction rate R B It is below 30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for disassembling an adhesive body comprising an adhesive sheet and the adhesive sheet itself.

[0002] This application claims priority based on Japanese Patent Application No. 2023-204737, filed on December 4, 2023, the entire contents of which are incorporated herein by reference. Background Technology

[0003] Generally, adhesives (also known as pressure-sensitive adhesives, hereinafter the same) have the following properties: they exist as soft solids (viscoelastics) in a temperature range near room temperature, and easily adhere to the adherends under pressure. By effectively utilizing these properties, adhesives are widely used in various fields, either as adhesive sheets with an adhesive layer on a support or as unsupported adhesive sheets. Furthermore, the aforementioned adhesives can be peeled off from the adherends by appropriate means after use, if necessary. Patent documents 1-3 are cited as examples of technical documents related to peeling adhesives from adherends.

[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2020-023656 Patent Document 2: Japanese Patent Application Publication No. 2021-138934 Patent Document 3: International Publication No. 2022 / 038926 Summary of the Invention

[0005] The problem that the invention aims to solve In recent years, from the perspective of reducing environmental impact and conserving resources, there has been a growing trend of separating adhesive-bonded components from finished products for reuse (recycling, reuse, etc.). For example, display devices (monitors) built into products with display functions such as smartphones, computers (desktop, laptop, tablet, etc.), and televisions have multi-layered structures containing various functional components, each made of different materials, such as liquid crystal displays, organic EL (electroluminescent) displays, and PDP (plasma display panels). Therefore, recycling and reuse are highly advantageous. Furthermore, in the processing, handling, and storage of glass, metals, and organic materials (such as PET, PI, etc.), it is known to adhere surface protectants to the surface to prevent damage and contamination. These surface protectants are then removed from the adhered material at an appropriate time after achieving their protective purpose. Other examples of applications requiring the removal of adhesive-based bonds at the desired time include battery mounting applications, where the bonds are more likely to be removed during the repair, replacement, or inspection of components that make up electronic devices.

[0006] However, the bonding reliability and ease of disassembly of adhesives are inversely related; there is a tendency for joints requiring high bonding reliability to become difficult to disassemble. For example, in the case of a joint formed by bonding rigid bodies together with an adhesive, it is impossible to deform the adhered parts to reduce the peeling force when disassembling the joint, and the force required to release the overall adhesive state of the joint surface tends to be large. In addition, sometimes the parts (adhesives) joined by adhesives are hard and brittle parts or thin-walled parts, and for such parts, there is a possibility of breakage due to the force exerted when peeling off the adhesive. In view of this situation, the inventors of this application proposed in Patent Document 1 an adhesive sheet (water-peelable adhesive sheet) that can be easily peeled off with water and has improved water resistance reliability during bonding.

[0007] However, the water-removable adhesive sheet proposed in Patent Document 1 is based on the premise of using water or other aqueous liquids for peeling the adhesive sheet from the adhered materials. Therefore, it can be appropriately applied to peeling from highly hydrophilic adhered materials such as glass and silicon wafers. On the other hand, it cannot be appropriately applied to adhered materials with low hydrophilicity. If a technology can be provided that simultaneously achieves bonding reliability and ease of disassembly not only for highly hydrophilic adhered materials but also for less hydrophilic adhered materials such as metals and resins, it would be beneficial to broaden the range of applicable adhered materials.

[0008] The present invention was made in view of the above circumstances, and its object is to provide a method for disassembling a joint that can also be applied to the disassembly of a joint containing components with low hydrophilicity, and simultaneously achieves both joint reliability and ease of disassembly. A related object is to provide an adhesive sheet that can be easily peeled off from components with low hydrophilicity using an alcoholic liquid.

[0009] Methods for solving problems According to this specification, a method for disassembling a joint comprising an adhesive sheet having a first adhesive surface and a first component engaging with the first adhesive surface is provided. The disassembly method includes: The aforementioned bond was immersed in a peeling solution mainly composed of a lower alcohol having 1 to 5 carbon atoms; and the bond was disassembled after immersion. In the peel test described below, the reduction rate R of the ethanol peel force N1 [N / 20mm] relative to the normal peel force N0 [N / 20mm] at the first measurement of the adhesive sheet was... A The percentage is over 70%. The average peel strength N0 of the above-mentioned adhesive sheet in the second measurement relative to the average peel strength N0 [N / 20mm] in the first measurement is... S [N / 20mm] reduction rate R B It can be below 30%.

[0010] [Peeling Test] (First measurement) The first adhesive surface of the adhesive sheet was adhered to a stainless steel plate and placed in an autoclave. The plate was then treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After removal from the autoclave, the plate was allowed to stand for 30 minutes at 23°C and 50% RH. Under the same conditions, the adhesive sheet was then peeled from the stainless steel plate using a tensile testing machine at a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol was added dropwise to the point where the adhesive sheet began to separate from the stainless steel plate. The peel strength observed before the addition of ethanol was designated as the normal peel force N0 [N / 20 mm], and the peel strength observed after the addition of ethanol was designated as the ethanol peel force N1 [N / 20 mm]. (Second measurement) After drying the adhesive sheet used in the first test, the first adhesive surface of the adhesive sheet was adhered to a new stainless steel plate. The plate was then placed in an autoclave and treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After being removed from the autoclave and allowed to stand for 30 minutes at 23°C and 50% RH, the adhesive sheet was peeled from the stainless steel plate using a tensile testing machine under the same conditions, with a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol was added dropwise to the point where the adhesive sheet began to separate from the stainless steel plate. The peel strength observed before the addition of ethanol was designated as the normal peel force N0. S [N / 20mm], the peel strength observed after ethanol addition will be defined as the ethanol peel force N1. S [N / 20mm].

[0011] According to the above disassembly method, the adhesive sheets constituting the laminate showed a decrease in peel force R caused by the addition of ethanol. A With an excellent alcohol-removable property of over 70%, the aforementioned bond can be efficiently disassembled by immersion in the aforementioned release solution (e.g., even with a short immersion time in the release solution). Furthermore, regarding the reduction rate R of the aforementioned adhesive sheet... B For joints with a content of 30% or less, in the normal use condition of the joint (i.e., the use condition where it is expected to maintain the adhesive sheet-based joint), contact with alcohol can exhibit a certain level or higher of durability. The disassembly method disclosed herein is useful, for example, as a method for efficiently disassembling joints possessing such alcohol resistance.

[0012] In some embodiments, it is preferred that the contact angle of the first component with distilled water is 50 degrees or more. The disassembly method disclosed herein is preferably implemented in a manner that allows for the disassembly of an assembly containing components with low hydrophilicity on their surfaces.

[0013] In some embodiments, the first adhesive surface described above may be the surface of an acrylic adhesive layer comprising an acrylic polymer as the base polymer. The disassembly method disclosed herein can preferably be implemented in a manner that disassembles the bond comprising the adhesive sheet of this configuration.

[0014] In some embodiments, the monomer components constituting the aforementioned acrylic polymers include alkyl (meth)acrylates having alkyl groups having 10 to 14 carbon atoms ((meth)acrylate C). 10-14 Alkyl esters are preferred. That is, the above-mentioned acrylic polymers contain (meth)acrylic acid C. 10-14 Polymers containing alkyl ester monomers are preferred. With an acrylic adhesive layer comprising such an acrylic polymer, the aforementioned reduction rate R can be suitably achieved. A High-adhesion sheet.

[0015] In some embodiments, the adhesive sheet may be a double-sided adhesive sheet with the surface opposite to the first adhesive surface serving as the second adhesive surface. In this embodiment, the joint may further include a second component that engages with the second adhesive surface. The disassembly method disclosed herein can also be preferably applied to the disassembly of such a joint in which the first and second components are joined by a double-sided adhesive sheet.

[0016] According to this specification, an adhesive sheet is provided, comprising: a first adhesive layer constituting a first adhesive surface; a second adhesive layer constituting a second adhesive surface, wherein the second adhesive surface is a surface opposite to the first adhesive surface; and a substrate disposed between the first adhesive layer and the second adhesive layer. In the peel test described below, the reduction rate R of the ethanol peel force N1 [N / 20mm] of the adhesive sheet relative to the normal peel force N0 [N / 20mm] is... A The weight loss rate is preferably less than 1% by weight when the substrate is immersed in ethanol for 10 minutes and then dried.

[0017] [Peeling Test] The first adhesive surface of the adhesive sheet was adhered to a stainless steel plate and placed in an autoclave. The plate was then treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After removal from the autoclave, the plate was allowed to stand for 30 minutes at 23°C and 50% RH. Under the same conditions, the adhesive sheet was then peeled from the stainless steel plate using a tensile testing machine at a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol was added dropwise to the point where the adhesive sheet began to separate from the stainless steel plate. The peel strength observed before the addition of ethanol was defined as the normal peel force N0 [N / 20 mm], and the peel strength observed after the addition of ethanol was defined as the ethanol peel force N1 [N / 20 mm].

[0018] It should be noted that the above-mentioned peeling test is equivalent to the first determination of the peeling test in the above-mentioned disassembly method.

[0019] The aforementioned adhesive sheet is constructed using a substrate that is substantially insoluble in ethanol, and the reduction in peel strength R caused by the addition of ethanol is shown. A It exhibits excellent alcohol-removing properties of 70%. Bonds formed using adhesive sheets (double-sided adhesive sheets with a substrate) having such a structure and properties can be easily disassembled, for example, by immersion in an alcohol-based release liquid (such as a release liquid primarily composed of lower alcohols having 1 to 5 carbon atoms). The aforementioned adhesive sheet is preferably used as a component of a bond that can be disassembled, for example, by any of the disassembly methods disclosed herein.

[0020] In some types of adhesive sheets, the ethanol absorption rate when the substrate is immersed in ethanol for 10 minutes is preferably 25% by weight or more of the substrate weight. Based on an adhesive sheet (double-sided adhesive sheet with substrate) having a substrate exhibiting such specified or higher ethanol absorption, when a joint including a joint based on the adhesive sheet is disassembled by immersing it in, for example, an alcoholic stripping liquid (a stripping liquid mainly composed of lower alcohols having 1 to 5 carbon atoms), the alcohol absorption of the substrate allows the stripping liquid to be efficiently distributed throughout the joint.

[0021] In some embodiments, the first adhesive layer described above may be an acrylic adhesive layer comprising an acrylic polymer as the base polymer. The adhesive sheet disclosed herein can preferably be implemented having the aforementioned acrylic adhesive layer.

[0022] In some embodiments, the monomer components constituting the above-mentioned acrylic polymer preferably include alkyl (meth)acrylates having an alkyl group having 10 to 14 carbon atoms (hereinafter also referred to as (meth)acrylate C). 10-14 Alkyl esters. ) Based on an acrylic adhesive layer containing such an acrylic polymer, the aforementioned reduction rate R can be suitably achieved. A High-adhesion sheet.

[0023] It should be noted that solutions obtained by appropriately combining the elements described in this specification may also be included within the scope of the invention claimed in this patent application. Attached Figure Description

[0024] [ Figure 1 This is a cross-sectional view schematically showing an example of a joint comprising an adhesive sheet.

[0025] [ Figure 2 [A cross-sectional view is shown schematically to illustrate another example of the construction of a joint including an adhesive sheet.]

[0026] [ Figure 3 This is a schematic cross-sectional view illustrating the structure of an adhesive sheet according to one embodiment. Detailed Implementation

[0027] The preferred embodiments of the present invention will be described below. It should be noted that, apart from the cases specifically mentioned in this specification, matters necessary for implementing the present invention can be understood by those skilled in the art based on the teachings regarding the implementation of the invention described in this specification and common technical knowledge at the time of application. The present invention can be implemented based on the disclosure in this specification and common technical knowledge in the field. Furthermore, in the following drawings, components or parts that perform the same function are sometimes labeled with the same reference numerals, and sometimes repeated descriptions are omitted or simplified. Additionally, the embodiments described in the drawings are schematic for the purpose of clearly illustrating the present invention and do not necessarily represent the actual dimensions or scales provided.

[0028] In this specification, the term "base polymer" in the adhesive refers to the main component of the rubber-like polymer contained in the adhesive. The aforementioned rubber-like polymer refers to a polymer that exhibits rubber-like elasticity in a temperature range near room temperature. Furthermore, in this specification, the term "main component," unless otherwise specified, refers to a component contained in an amount of more than 50% by weight.

[0029] In this specification, the term "acrylic polymer" refers to a polymer derived from a monomeric component comprising more than 50% by weight of an acrylic monomer. The aforementioned acrylic monomer refers to a monomer derived from a monomer having at least one (meth)acryloyl group in one molecule. Furthermore, in this specification, the term "(meth)acryloyl" broadly refers to both acryloyl and methacryloyl groups. Therefore, the concept of acrylic monomers as used herein can include both monomers having an acryloyl group (acrylic monomers) and monomers having a methacryloyl group (methacrylic monomers). Similarly, in this specification, the term "(meth)acrylic acid" broadly refers to both acrylic acid and methacrylic acid, and the term "(meth)acrylate" broadly refers to both acrylates and methacrylates. Other similar terms are used in the same way.

[0030] In this manual, "weight" can be used interchangeably with "mass". For example, "weight%" can be used interchangeably with "mass%", and "parts by weight" can be used interchangeably with "parts by mass".

[0031] <Characteristics of Adhesive Sheets> (Peel force reduction rate R) A ) The adhesive sheet disclosed herein has a first adhesive surface (typically, the surface of a first adhesive layer). The rate of reduction in peel force (i.e., the rate of reduction in peel force caused by the addition of ethanol) was measured by adding ethanol dropwise during the peeling process after the first adhesive surface was adhered to a stainless steel plate. A The reduction rate of peel force is over 70%. AThe peel force reduction rate R can be determined through the peel test described above (the first and second measurements are performed in this peel test, based on the results of the first measurement). More specifically, the peel force N0 [N / 20 mm] and the ethanol peel force N1 [N / 20 mm] are measured through the peel test described in the following examples, and the obtained values ​​are substituted into the following formula to calculate the peel force reduction rate R. A .

[0032] Peel force reduction rate R A [%]=((N0-N1) / N0)×100 Peel force reduction rate R A For adhesive sheets with a peel strength reduction rate of over 70%, a good tendency to reduce peel strength is observed in alcohol-based release agents (e.g., release agents primarily composed of lower alcohols with 1 to 5 carbon atoms). These adhesive sheets are preferably used to construct adhesive bodies intended for disassembly using the disassembly method disclosed herein. Adhesive bodies constructed using the above-described adhesive sheets can be efficiently disassembled using the disassembly method disclosed herein. From the viewpoint of shortening the disassembly time and reducing the load on the components constituting the adhesive body during the disassembly operation, in some cases, the peel strength reduction rate R... A A peel strength reduction rate of 75% or higher is advantageous, preferably 80% or higher, more preferably 85% or higher, and can be 90% or higher. Peel strength reduction rate R A It can be 100%. From the perspective of ease of control of disassembly and stripping operations, less than 100% is appropriate in some methods, such as 99% or less or 98% or less.

[0033] (Peel force reduction rate R) B ) In some of the techniques disclosed herein, regarding the aforementioned adhesive sheet, the typical peel force N0 in the second measurement relative to the typical peel force N0 [N / 20mm] in the first measurement in the aforementioned peel test... S [N / 20mm] reduction rate (typical peel force reduction rate) R B For example, a reduction of 70% or less is appropriate. More specifically, the aforementioned typical peel strength reduction rate R B The following calculations were performed: the typical peel force N0 [N / 20mm] and the typical peel strength N0 were determined by the peel test described in the examples below. S Substitute the obtained value into the following formula to calculate the result.

[0034] Typically, the peel strength reduction rate R B [%] = ((N0-N0) S ) / N0)×100 The above-mentioned typical peel strength reduction rate R BThis can be understood as an indicator indicating the extent to which the normal peel force of an adhesive sheet peeled from the adherend (ethanol peel) by supplying ethanol to the interface between the first adhesive layer and the adherend (stainless steel plate) decreases compared to the original (before ethanol supply) normal peel force of the adhesive sheet. For example, in an adhesive sheet with a first adhesive layer that is too easily dissolved in ethanol, or a first adhesive layer that swells excessively due to contact with ethanol, resulting in a significant reduction in the cohesiveness of the surface portion, during ethanol peel, the adhesive constituting the first adhesive layer may be lost due to dissolution into ethanol, residue on the surface of the adherend, etc., or the surface smoothness of the first adhesive layer may be damaged. Therefore, the second normal peel force N0 may decrease compared to the normal peel force N0 measured in the first test. S The peel strength is significantly reduced, and in severe cases, even if a second test is desired, it becomes impossible to adhere the adhesive sheet to a new substrate (stainless steel plate). From the viewpoint of improved durability of the aforementioned joint in relation to alcohol contact under normal use conditions of the joint including the adhesive sheet (i.e., the expectation of maintaining the adhesive sheet-based joint condition), the reduction rate R of the adhesive sheet's normal peel strength is... B However, a higher peel strength becomes advantageous. Furthermore, it is preferable from the viewpoint of improving the reusability (re-adhesion) of the adhesive sheet after it has been separated from the adhered material using an alcohol-based peeling liquid. For example, in a joint where a first component and a second component are joined by an adhesive sheet, after separating the first component from the adhesive sheet using the disassembly method disclosed herein, the separated adhesive sheet (which may be in a state where the adhesion between the second adhesive surface and the second component is maintained) is used to construct a new joint, typically resulting in a lower peel strength R. B Suppression can become advantageous.

[0035] In some methods, the peel force reduction rate R is typically... B It is advantageous for the peel strength to be below 50%, preferably below 30%, more preferably below 25%, even more preferably below 20%, and can be below 15%, below 10%, below 9.0%, or below 8.0%, or below 7.0%, below 5.0%, or below 3.0%. Additionally, the peel strength reduction rate R is typically... B Typically, it is above 0% (e.g., greater than 0%). From a practical point of view, such as considering the balance with other performance and characteristics, it can be above 0.5%, above 1.0%, above 1.5%, or above 2.0%.

[0036] (Typically, the peel force is N0) In the technology disclosed herein, the typical peel force N0 of the adhesive sheet is not particularly limited, and can be, for example, 0.2 N / 20 mm or more. In some embodiments, from the viewpoint of bonding reliability during normal use, the typical peel force N0 is preferably 0.5 N / 20 mm or more, more preferably 0.7 N / 20 mm or more, even more preferably 1.2 N / 20 mm or more (e.g., 1.5 N / 20 mm or more), and can be 2.0 N / 20 mm or more, 3.0 N / 20 mm or more, 4.0 N / 20 mm or more, 5.0 N / 20 mm or more, or 6.0 N / 20 mm or more. Adhesive sheets or joints containing such adhesive sheets with higher typical peel forces N0 can better achieve a peel force reduction rate R. A In order to provide the advantages mentioned above, in some other ways, from a practical point of view, such as considering the balance with other performance and characteristics, the typical peel force N0 of the adhesive sheet can be, for example, less than 50 N / 20 mm, less than 40 N / 20 mm, less than 30 N / 20 mm, less than 25 N / 20 mm, less than 20 N / 20 mm, or less than 15 N / 20 mm.

[0037] The above description of the upper and lower limits of the normal peel force N0 (normal peel force N0 at the first measurement) of the adhesive sheet also applies to the normal peel force N0 at the second measurement. S Upper and lower limits.

[0038] (Ethanol peeling force N1) In the technology disclosed herein, the ethanol peel force N1 of the adhesive sheet only needs to satisfy any one of the peel force reduction rates R mentioned above. A This is acceptable, without particular limitation. From the viewpoint of ease of disassembly and peeling provided by the alcohol-based stripping solution, in some methods, an ethanol stripping force N1 of, for example, 1.5 N / 20 mm or less is suitable, 1.0 N / 20 mm or less is advantageous, preferably less than 1.0 N / 20 mm, more preferably less than 0.8 N / 20 mm, and can be less than 0.5 N / 20 mm, less than 0.4 N / 20 mm, or less than 0.3 N / 20 mm. An ethanol stripping force N1 of 0 N / 20 mm or more is suitable in some methods from the viewpoint of ease of control of disassembly and peeling operations, and can be, for example, more than 0 N / 20 mm, or more than 0.05 N / 20 mm.

[0039] The above description of the upper and lower limits of the ethanol peel strength N1 (ethanol peel strength N1 at the first measurement) of the adhesive sheet also applies to the ethanol peel strength N2 at the second measurement. S Upper and lower limits.

[0040] (Peel force reduction rate R)AS ) In some of the techniques disclosed herein, the adhesive sheet, in the aforementioned peel test, exhibits a peel force N0 relative to the usual peel force during the second measurement. S Ethanol peel strength N1 in terms of [N / 20mm] S The rate of decrease in [N / 20mm] (i.e., the rate of decrease in peel force caused by the addition of ethanol during the second measurement) R AS For example, a reduction of 55% or less is appropriate. More specifically, the aforementioned peel force reduction rate R... A The following calculation shows that the typical peel force N0 is determined by the peel test described in the examples below. S [N / 20mm] and ethanol peel strength N1 S [N / 20mm], substitute the obtained value into the following formula to calculate it.

[0041] Peel force reduction rate R AS [%] = ((N0) S -N1 S ) / N0 S )×100 Regarding the reduction rate of peel force R AS Regarding the adhesive sheet that has been suppressed, in the case of reusing the adhesive sheet after it has been peeled from the substrate using an alcohol-based release agent (e.g., by attaching it to a new substrate), good alcohol-based release properties are maintained during the reuse process. Therefore, it is possible to suitably achieve both bonding reliability and ease of disassembly and peeling during reuse. In some cases, the peel force reduction rate R... AS A peel strength reduction rate of 70% or higher is advantageous, preferably 75% or higher or 80% or higher, more preferably 85% or higher, and can be 90% or higher or higher. Peel strength reduction rate R AS It can be 100%, and in some ways less than 100% is appropriate; it can be below 99% or 98%.

[0042] It should be noted that, regarding the stainless steel plate (SUS430BA plate) used as the adherend in the peel test described above, the contact angle of the surface to which the adhesive sheet is bonded with distilled water is approximately 80 degrees, and the contact angle with ethanol is approximately 10 degrees. In the embodiments described later, the stainless steel plate (SUS430BA plate) used as the adherend and the first component of the bond in the peel test is also the same.

[0043] <Joint containing adhesive sheets> According to this specification, a joint (also understood as a component with an adhesive sheet) is provided, comprising at least the aforementioned adhesive sheet and a first component engaging with a first adhesive surface of the adhesive sheet. The adhesive sheet has one or more of the characteristics described above (e.g., at least a peel strength reduction rate R). A Adhesive sheets (within any of the above ranges) can preferably be used as constituent elements of such a joint.

[0044] The adhesive sheet included in the aforementioned joint can be, for example, a substrate-free adhesive sheet formed solely of an adhesive layer. A substrate-free adhesive sheet is typically a double-sided adhesive sheet (a substrate-free double-sided adhesive sheet) where one surface of the adhesive layer is a first adhesive surface and the other surface (the surface opposite to the first adhesive surface) is a second adhesive surface. Figure 1 As shown, by joining the first adhesive surface 11a of the adhesive sheet 1 (adhesive layer 11) to the first component 61 and joining the second adhesive surface 11b to the second component 62, a joint body 100 can be formed by joining the first component 61 and the second component 62 through the adhesive sheet 1. Therefore, the first component can be understood as the object to which the first adhesive surface of the adhesive sheet is attached. Similarly, the second component can be understood as the object to which the second adhesive surface of the adhesive sheet is attached. The adhesive sheet before use can be in a form that protects the first adhesive surface and the second adhesive surface with their respective release liner (typically, at least the side in contact with the adhesive surface becomes the release liner).

[0045] The adhesive sheet included in the above-mentioned joint can be, for example, such as Figure 2 As shown in the embodiment, the adhesive sheet 2 included in the joint body is a double-sided adhesive sheet with a substrate, having a first adhesive layer 11 on the first surface 20a side of the substrate 20 and a second adhesive layer 12 on the second surface side (opposite to the first surface) 20b. Regarding the adhesive sheet 2, by joining the first adhesive surface 11a (the surface of the first adhesive layer 11) to the first component 61 and joining the second adhesive surface 12a (the surface of the second adhesive layer 12) to the second component 62, a joint body 200 can be constructed by joining the first component 61 and the second component 62 via the adhesive sheet 2. The adhesive sheet 2 before use can be, for example, such as... Figure 3As shown, the adhesive sheet 50 with release liner is a component in which the first adhesive surface 11a and the second adhesive surface 12a are each protected by release liner (typically, at least one side of the release liner in contact with the adhesive surface is the release surface) 31, 32. As release liner 31, 32, for example, release liner configured such that a release layer based on a release agent is provided on one side of a sheet-like substrate (pad substrate), making that side the release surface. Alternatively, the release liner 32 can be omitted, and a release liner 31 with both sides as release surfaces can be used, overlapped with the adhesive sheet 2 and wound into a spiral shape, thereby forming an adhesive sheet with release liner in a form where the second adhesive surface 12a is protected against the back of the release liner 31 (roll form).

[0046] The release liner is not particularly limited and can be, for example, a release liner whose surface has been peeled off from a liner substrate such as a resin film or paper, or a release liner formed from a low-adhesion material such as a fluoropolymer (polytetrafluoroethylene, etc.) or a polyolefin resin (polyethylene, polypropylene, etc.). In the aforementioned peeling treatment, for example, silicone-based or long-chain alkyl-based release agents can be used. In some embodiments, a peeled resin film is preferably used as the release liner.

[0047] Furthermore, the adhesive sheet included in the joint disclosed herein can be a single-sided adhesive sheet having an adhesive layer on a first side of a substrate, with the surface of the adhesive layer serving as a first adhesive surface; or it can be a single-sided adhesive sheet having a first adhesive layer on a first side of a first substrate, a second adhesive layer on a second side of the same first substrate, and a second substrate bonded to the surface of the second adhesive layer (the surface opposite to the first substrate side). By bonding the first adhesive surface of such a single-sided adhesive sheet to a first component, a joint (a component with adhesive) including the first component and the aforementioned single-sided adhesive sheet can be constructed.

[0048] It should be noted that, Figure 1 , Figure 2 In the illustrated embodiment, the first component, the second component, and the adhesive sheet constituting the joint are all configured as layers, sheets, or plates, and the joint has the form of a laminated structure (laminated body). However, the shapes of the first component, the second component, and the adhesive sheet may not be layered, sheet-like, or plate-like; they can have various shapes. For example, the first component only needs to have a surface that joins with the first adhesive surface of the adhesive sheet. Depending on the application and purpose, it can also have complex shapes, curved shapes, and other three-dimensional component shapes. The adhesive sheet can also have various shapes to match the surface shapes of the first component and the second component.

[0049] Furthermore, in this specification, the term "component" in "component 1" and "component 2" is used to mean a constituent element of the assembly, and is not specifically limited to that meaning. For example, component 1 and component 2 can be separate articles or components, or they can each be components constituting other articles.

[0050] In addition to the first component and the second component, the joint may optionally include other components or constituent elements. For example, if the first component is part of an electronic device or other article of manufacture, the joint may be composed of multiple components or elements.

[0051] The materials of the first and second components are not particularly limited. The materials of at least the constituent surfaces of each component can be, for example, metals such as stainless steel (SUS) and aluminum; glass such as alkali glass and alkali-free glass; resins such as acrylic resin, ABS resin, polycarbonate resin, and polystyrene resin; and so on. The surfaces for bonding the first or second adhesive surfaces can be coated surfaces of acrylic, polyester, alkyd, melamine, urethane, acid-epoxy cross-linked, or composite systems (such as melamine acrylic and melamine alkyd), or coated surfaces of galvanized steel sheets.

[0052] In some embodiments, the contact angle (hereinafter also referred to as the water contact angle) of the surface of the first component for bonding with the first adhesive surface to distilled water can be, for example, 30 degrees or more or 40 degrees or more. In some preferred embodiments, the water contact angle of the aforementioned bonding surface can be 50 degrees or more, 60 degrees or more (e.g., greater than 60 degrees), 70 degrees or more, 75 degrees or more, or 80 degrees or more. According to the technology disclosed herein, in a joint in which the first adhesive surface of the adhesive sheet is bonded to such a surface with low hydrophilicity, it is also possible to suitably achieve both bonding reliability and ease of disassembly.

[0053] Furthermore, it is suitable for the water contact angle of the surface of the first component to be less than 150 degrees, advantageous to be less than 120 degrees, and preferably less than 100 degrees (e.g., less than 90 degrees). The technology disclosed herein can also be implemented with the water contact angle of the aforementioned surface being, for example, less than 75 degrees, less than 65 degrees, less than 55 degrees, less than 45 degrees, less than 35 degrees, less than 25 degrees, or less than 15 degrees. The lower limit of the water contact angle is in principle 0 degrees. In some embodiments, the water contact angle of the aforementioned surface can be, for example, greater than 0 degrees, greater than 1 degree, greater than 3 degrees, or greater than 5 degrees.

[0054] The above description regarding the water contact angle of the first component also applies to the water contact angle of the second component in a joint that includes a second component in addition to the first component. In some embodiments, the water contact angle of at least the joint surface of the first component is preferably 50 degrees or more (e.g., 50 degrees or more and 100 degrees or less), more preferably 60 degrees or more, 65 degrees or more, 70 degrees or more, or 80 degrees or more.

[0055] In some embodiments, the contact angle (hereinafter also referred to as the ethanol contact angle) of the surface of the first component for bonding with the first adhesive surface can be, for example, less than 60 degrees, preferably less than 50 degrees. In some preferred embodiments, the ethanol contact angle of the aforementioned surface is less than 40 degrees, more preferably less than 30 degrees (e.g., less than 25 degrees), and can be less than 20 degrees or less or less than 15 degrees. If the ethanol contact angle of the component surface becomes small, the alcohol liquid becomes more likely to wet and spread along the surface, and there is a tendency for increased disintegration due to immersion in an alcoholic stripping liquid. The lower limit of the ethanol contact angle is in principle 0 degrees. In some embodiments, the ethanol contact angle of the aforementioned surface can be, for example, greater than 0 degrees, more than 1 degree, more than 3 degrees, or more than 5 degrees.

[0056] The above description of the ethanol contact angle of the first component can also be applied to the ethanol contact angle of the second component in a joint that includes a second component in addition to the first component.

[0057] It should be noted that the contact angles of the aforementioned interface with ethanol and with distilled water were measured as follows. Specifically, under a measurement atmosphere of 23°C and 50% RH, a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., trade name "DMo-501 type", control box "DMC-2", control and analysis software "FAMAS (version 5.0.30)") was used, and the measurement was performed using the droplet method. The amount of ethanol added for measuring the contact angle with ethanol and the amount of distilled water added for measuring the contact angle with distilled water were each set to 2 μL. The contact angle was calculated using the Θ / 2 method based on the image after 5 seconds of droplet addition (implemented at N5).

[0058] In some embodiments, the aforementioned joint has a configuration in which a first component and a second component are joined by an adhesive sheet, and both the first and second components are rigid bodies. With respect to joints where both the first and second components are rigid bodies, there is a situation where, when disassembling the joint, it is impossible to deform the adhered components (increasing the peel angle) to reduce the peeling force, and releasing the overall adhesive state of the joint surfaces (e.g., the joint surface between the first component and the first adhesive surface) requires considerable force, making disassembly difficult by human force. According to the disassembly method disclosed herein, even with this configuration, the first and second components can be separated efficiently (e.g., after immersion in an alcoholic peeling solution for a short time). The materials of the first and second components can be the same or different. Examples of materials suitable for use as rigid bodies for the first and second components include materials made of metals (stainless steel, aluminum, etc.), glass, hard resin, or ceramics.

[0059] The term "rigid body" as used herein refers to an object with rigidity and dimensions that are substantially indeformable by human intervention. In this specification, it refers to an object whose deformability can not be improved by human intervention (generally based on an adult male) when the joined parts are disassembled. Although not specifically limited, the term "rigid body" in this specification refers to an object that satisfies at least one of the following: a tensile modulus of elasticity of 1 × 10⁻⁶. 10 Pa or above; and bending stiffness of 0.01 Pa·m 3 above.

[0060] The tensile modulus of elasticity mentioned above refers to the tensile modulus of elasticity measured in accordance with JIS K7161. More specifically, it is measured by the following method.

[0061] [Tension Test] The object to be measured is cut into strips with a width of 10 mm to prepare test pieces. Following JIS K7161, the test pieces are stretched under the following conditions to obtain the stress-strain curves.

[0062] (Extended conditions) Measurement temperature: 25℃ Stretching speed: 300mm / minute Chuck spacing: 50mm As a tensile testing machine, a universal tensile-compression testing machine (device name "Tensile-Compression Testing Machine, TCM-1kNB", manufactured by Minebea) or its equivalent can be used.

[0063] The tensile modulus of elasticity can be obtained by linear regression of the stress-strain curves described above.

[0064] In addition, regarding the aforementioned bending stiffness value D [Pa·m] 3 For example, if the thickness of the material is set as h [m], the Poisson's ratio of the material is set as ν, and the tensile modulus of elasticity is set as E [Pa], then the value is obtained by the following formula: D = Eh 3 / 12(1-ν 2 ).

[0065] The thickness of the glass (e.g., glass plate), metal (e.g., metal plate), and ceramic (e.g., ceramic plate) that can be used as the first and / or second component is not particularly limited, but may be, for example, about 0.1 mm or more, or about 0.5 mm or more. Glass, metal, and ceramic materials with thicknesses within the above range can possess the properties of a rigid body; therefore, the application of the technology disclosed herein has significant advantages. The maximum thickness of the aforementioned glass, metal, and ceramic materials is not particularly limited, and may be approximately 30 cm or less, approximately 10 cm or less, approximately 1 cm or less, approximately 5 mm or less, or approximately 2 mm or less.

[0066] Additionally, as a resin material (typically a plastic material) suitable for use as the first component and / or the second component, a material satisfying at least one of the following can be used: a tensile modulus of elasticity of 1 × 10⁻⁶. 10 Pa or above; and bending stiffness of 0.01 Pa·m 3 The above describes the types of resin materials used. Examples of resin materials include polyester resin, acrylic resin, ABS resin, polycarbonate resin, polystyrene resin, and polyimide resin. While not specifically limited, the thickness of these resin materials can be, for example, approximately 1 mm or more, approximately 2 mm or more, 3 mm or more, 5 mm or more, or 1 cm or more. Resin materials with thicknesses within these ranges can possess the properties of a rigid body; therefore, the application of the technology disclosed herein has significant advantages. The maximum thickness of the resin materials is not specifically limited; it can be approximately 30 cm or less, approximately 10 cm or less, or approximately 1 cm or less.

[0067] <Adhesive layer> The adhesive sheet disclosed herein comprises at least an adhesive layer (first adhesive layer) constituting a first adhesive surface of the adhesive sheet. The type of adhesive constituting the first adhesive layer is not particularly limited. The adhesive may be, for example, an adhesive comprising one or more adhesives selected from a variety of known adhesives, such as acrylic adhesives, rubber adhesives (natural rubber, synthetic rubber, mixtures thereof, etc.), silicone adhesives, polyester adhesives, urethane adhesives, polyether adhesives, polyamide adhesives, and fluorinated adhesives. Here, acrylic adhesives refer to adhesives whose main component is an acrylic polymer (base polymer). The same meaning applies to rubber adhesives and other adhesives.

[0068] Acrylic adhesives In some methods, acrylic adhesives are preferred as constituent materials of the adhesive. Acrylic adhesives offer a high degree of design freedom in terms of physical properties and characteristics, making them suitable for creating adhesive sheets that can form bonds that combine reliable bonding with easy disassembly.

[0069] (Acrylic polymer) The acrylic polymers used as base polymers in the technology disclosed herein can be, for example, acrylic polymers composed of monomeric components comprising alkyl (meth)acrylates having a straight-chain or branched alkyl group having 1 to 20 carbon atoms at the ester terminus. Hereinafter, alkyl (meth)acrylates having an alkyl group having X to Y carbon atoms at the ester terminus will sometimes be referred to as "(meth)acrylate C". X-Y Alkyl esters. In some approaches, to facilitate a balance of properties, the (meth)acrylic acid C in the monomer components of acrylic polymers is selected. 1-20 The content of alkyl esters is preferably 50% by weight or more, and more than 65% by weight or 70% by weight, and can be more than 75% by weight, more than 80% by weight, or more than 85% by weight. The (meth)acrylic acid C in the above monomer components... 1-20 The alkyl ester content can be 100% by weight, but from the viewpoint of the adhesive's cohesiveness and adhesion to polar substrates, it can be, for example, 99.9% by weight or less, 99% by weight or less, 98% by weight or less, or 95% by weight or less. (Meth)acrylic acid C 1-20 Alkyl esters can be used alone or in combination of two or more.

[0070] In some embodiments, the monomer components constituting the acrylic polymer preferably include one or more (meth)acrylic acid Cs. 4-20 Alkyl esters, more preferably containing one or more (meth)acrylic acids C 4-18 Alkyl ester. The technology disclosed herein can be preferably implemented in the form of disassembling an adhesive sheet comprising an adhesive layer having an adhesive layer containing the acrylic polymer as a base polymer, or in the form of a double-sided adhesive sheet with a substrate having the aforementioned adhesive layer.

[0071] It should be noted that, in this specification, the term "monomer component constituting the acrylic polymer" or "monomer component of the acrylic polymer" refers to the monomer component of the acrylic polymer contained in the adhesive (layer). In the adhesive composition used to form the aforementioned adhesive (layer), the monomer component may be contained in the form of an unreacted monomer (i.e., in the form of a raw material monomer whose polymeric functional groups have not reacted), in the form of a polymer (i.e., as a monomer unit), or in both forms.

[0072] In some embodiments, the monomer components constituting the acrylic polymer preferably include (meth)acrylic acid C. 10-14Alkyl esters. Based on acrylic adhesive layers containing this acrylic polymer, good alcohol-removable properties are readily obtained. The reason for this is not particularly limiting, but it is believed that the C... 10-14 The alkyl side chains impart moderate hydrophobicity to the surface of the acrylic adhesive layer, thereby allowing the alcohol-based release agent to easily wet and spread along this surface, which contributes to improved alcohol release properties. As (meth)acrylic acid C 10-14 Specific examples of alkyl esters include decyl acrylate, lauryl acrylate (LA), tetradecyl acrylate, decyl methacrylate, lauryl methacrylate, and tetradecyl methacrylate. (Meth)acrylic acid C 10-14 Alkyl esters can be used alone or in combination of two or more.

[0073] (Meth)acrylic acid C in the monomer components of acrylic polymers 10-14 The alkyl ester content can be, for example, 1% by weight or more. From the viewpoint of alcohol stripping properties, it is preferably 3% by weight or more or 5% by weight or more, more preferably 10% by weight or more or 15% by weight or more, and can be 20% by weight or more, 25% by weight or more, 30% by weight or more, 40% by weight or more, or 45% by weight or more, or 50% by weight or more. Furthermore, the (meth)acrylic acid C in the monomer component of the acrylic polymer... 10-14 The alkyl ester content can be, for example, less than 95% by weight, less than 90% by weight, or less than 80% by weight. In some cases, considering the balance between alcohol-free properties and other characteristics, the (meth)acrylic acid C in the above monomer components... 10-14 It is appropriate for the alkyl ester content to be less than 75% by weight, it is advantageous to be less than 70% by weight, preferably less than 65% by weight, it can be less than 60% by weight, it can be less than 55% by weight, less than 50% by weight, or less than 50% by weight (e.g., less than 45% by weight, less than 40% by weight, or less than 35% by weight).

[0074] In some embodiments, the monomer components constituting the acrylic polymer may include (meth)acrylic acid C. 4-9 Alkyl ester. (Meth)acrylic acid C 4-9 Alkyl esters (e.g., C14 acrylate) 4-9 Alkyl esters can contribute to improved adhesive flexibility and bonding properties (such as peel strength). As a (meth)acrylic acid C 4-9Specific examples of alkyl esters include butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and isononyl (meth)acrylate. (Methacrylic acid C) 4-9 Alkyl esters can be used alone or in combination of two or more. For example, the monomeric components mentioned above preferably include either or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA).

[0075] (Meth)acrylic acid C in the monomer components of acrylic polymers 4-9 The content of alkyl esters can be, for example, 1% by weight or more. From the viewpoint of obtaining better performance, it is preferable to be 5% by weight or more or 10% by weight or more, more preferably 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, or 50% by weight or more, 55% by weight or more, or 60% by weight or more. Furthermore, the monomer component of the acrylic polymer contains (meth)acrylic acid C. 4-9 The alkyl ester content can be, for example, 95% by weight or less. From the viewpoint of easily obtaining good alcohol stripping properties, it is advantageous to be 90% by weight or less, preferably 85% by weight or less, and can be 80% by weight or less, 75% by weight or less, or 70% by weight or less.

[0076] In some methods, the monomer components constituting the acrylic polymer can be combined to include one or more (meth)acrylic acid Cs. 4-9 Alkyl esters, and one or more (meth)acrylic acids C 10-14 Alkyl esters. From the viewpoint of easily obtaining good alcohol-stripping properties, in some ways, the monomer component of the acrylic polymer, relative to (meth)acrylic acid C... 4-9 (Meth)acrylic acid C in relation to alkyl esters 10-14 Content ratio of alkyl esters based on weight (C) 10-14 / C 4-9 The content is preferably 0.1 or more, more preferably 0.3 or more. In some methods, the above-mentioned content ratio (C) 10-14 / C 4-9 The content can be 0.5 or higher, 0.8 or higher, 1.0 or higher, 1.2 or higher, 1.4 or higher, 1.8 or higher, or 2.0 or higher. In some methods, considering the uniformity of adhesive performance, the above content ratios (C) are... 10-14 / C 4-9The value is preferably 10 or less, more preferably 5.0 or less, can be 4.0 or less, or can be 3.0 or less.

[0077] The monomer components constituting the above-mentioned acrylic polymers may include alkyl (meth)acrylates, and other monomers (copolymeric monomers) capable of copolymerizing with alkyl (meth)acrylates, as needed. Preferred copolymeric monomers are monomers with polar groups (e.g., nitrogen-containing rings, hydroxyl groups, carboxyl groups, etc.) and monomers with high glass transition temperatures (e.g., above 10°C) in homopolymers. Monomers with polar groups can help introduce crosslinking points into the acrylic polymer or improve the cohesive strength of the adhesive. One copolymeric monomer may be used alone, or two or more may be used in combination.

[0078] Non-limiting examples of copolymerizable monomers include: monomers having a nitrogen-containing ring, monomers containing hydroxyl groups, monomers containing carboxyl groups, monomers containing anhydride groups, monomers containing sulfonic acid or phosphoric acid groups, monomers containing epoxy groups, monomers containing cyano groups, monomers containing isocyanate groups, monomers containing amide groups, monomers containing amino groups, monomers having a succinimide skeleton, maleimides, aminoalkyl methacrylates, alkoxy-containing monomers, alkoxysilyl-containing monomers, vinyl esters, vinyl ethers, aromatic vinyl compounds, alkenes, (meth)acrylates having alicyclic hydrocarbon groups, (meth)acrylates having aromatic hydrocarbon groups, and (meth)acrylates containing heterocyclic rings such as tetrahydrofurfuryl methacrylate, (meth)acrylates containing halogen atoms such as vinyl chloride and fluorine atoms, (meth)acrylates containing silicon atoms such as organosilicon (meth)acrylates, and (meth)acrylates obtained from terpene compound derivative alcohols, etc.

[0079] Examples of monomers having a ring containing a nitrogen atom include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazolium, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-(meth)acryloylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisooxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc. (e.g., N-vinyl-2-caprolactam and other lactams).

[0080] Examples of hydroxyl-containing monomers include 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, 8-hydroxyoctyl methacrylate, 10-hydroxydecyl methacrylate, 12-hydroxylaurate methacrylate, methyl methacrylate (4-hydroxymethylcyclohexyl) methacrylate, and other hydroxyalkyl methacrylates.

[0081] Examples of (meth)acrylates containing alicyclic hydrocarbon groups include cyclopentyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, and adamantane methacrylate.

[0082] Examples of monomers containing carboxyl groups include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0083] When using such a comonomer, its dosage (or the total dosage when using multiple comonomers) is not particularly limited and can be set to, for example, 0.01% by weight or more of the monomer component. From the viewpoint of better utilizing the comonomer, the dosage can be 0.1% by weight or more of the total monomer component, or even 0.5% by weight or more. Furthermore, from the viewpoint of easily obtaining a balanced adhesive property, it is appropriate for the dosage of the comonomer to be 60% by weight or less of the total monomer component, or even 50% by weight or less, or 40% by weight or less.

[0084] In some embodiments, the monomer component constituting the acrylic polymer may include a monomer having a nitrogen atom. By using a monomer having a nitrogen atom, it is possible to achieve both good alcohol peeling properties and general peeling force more effectively. As a monomer having a nitrogen atom, monomers having nitrogen-containing functional groups (nitrogen-containing rings, amide groups, amino groups, etc.) as exemplified above can be used. Suitable examples of monomers having a nitrogen atom include monomers having nitrogen-containing rings. For example, N-vinylcyclic amides can be used, with N-vinyl-2-pyrrolidone (NVP) being preferred. A single monomer having a nitrogen atom can be used, or two or more can be used in combination. The content of the monomer having a nitrogen atom (preferably a monomer having a nitrogen-containing ring) in the monomer component can be, for example, 0.5% by weight or more, 1% by weight or more is appropriate from the viewpoint of obtaining higher performance, 3% by weight or more is advantageous, 5% by weight is preferred, and it can be 7% by weight or more, 8% by weight or more, or 9% by weight or more. In addition, from the viewpoint of avoiding excessive hydrophilicity of the adhesive layer, it is appropriate for the content of the monomer with nitrogen atom (preferably the monomer with a ring containing nitrogen atom) in the monomer component to be 40% by weight or less, preferably 30% by weight or less, and can be 25% by weight or less, 20% by weight or less, 15% by weight or less or 12% by weight or less.

[0085] In some preferred embodiments, the monomer components constituting the acrylic polymer may be combined to include (meth)acrylic acid C. 10-14 Alkyl esters and monomers having nitrogen atoms (preferably monomers having a ring containing nitrogen atoms). In this manner, the (meth)acrylic acid C content in the monomer component of the acrylic polymer, relative to the monomer having nitrogen atoms (preferably the monomer having a ring containing nitrogen atoms), is... 10-14 Content ratio of alkyl esters based on weight (C) 10-14 The content ratio (containing N monomers) is preferably 1 or more (e.g., 3 or more), and can be 5 or more, or 10 or more. 10-14 The content of N-containing monomers is preferably below 10,000, but can be below 5,000, below 3,000, or below 2,000. In some methods, the above content ratio (C) is... 10-14 (Containing N monomers) can be below 1000, below 500, below 200, below 80, below 40, or below 20.

[0086] Combination use of (meth)acrylic acid C 10-14 In some ways, alkyl esters and monomers having nitrogen atoms (preferably monomers having a ring containing nitrogen atoms) constitute the monomeric component of acrylic polymers, in which (meth)acrylic acid C 10-14The total content of alkyl esters and nitrogen-containing monomers (preferably monomers with nitrogen-containing rings) is preferably 8% by weight or more or 10% by weight or more, more preferably 15% by weight or more or 20% by weight or more, and can be 25% by weight or more, 30% by weight or more, or 35% by weight or more. Furthermore, in some embodiments, the proportion of (meth)acrylic acid C in the monomer components constituting the acrylic polymer is... 10-14 The total content of alkyl esters and monomers having nitrogen atoms (preferably monomers having a ring containing nitrogen atoms) can be, for example, 95% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less, or 50% by weight or less.

[0087] In some embodiments, the monomer components constituting the acrylic polymer may include hydroxyl-containing monomers. Hydroxyl-containing monomers can help adjust the cohesive strength and degree of crosslinking (e.g., crosslinking based on isocyanate crosslinking agents) of the adhesive. Hydroxyl-containing monomers such as those described above can be used, for example, 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA) are preferably used. One hydroxyl-containing monomer can be used alone, or two or more can be used in combination. The amount of hydroxyl-containing monomer used is not particularly limited. For example, the content of the hydroxyl-containing monomer in the monomer component can be 0.5% by weight or more, 1% by weight or more, 3% by weight or more, or 5% by weight or more. In some embodiments, from the viewpoint of suppressing the decrease in alcohol peelability due to excessive hydrophilicity of the adhesive layer, the content of the hydroxyl-containing monomer in the monomer component is appropriate to be 30% by weight or less, preferably 25% by weight or less or 20% by weight or less, more preferably 15% by weight or less, 12% by weight or less, 10% by weight or less, or 8% by weight or less. The technology disclosed herein can preferably be implemented in such a manner that the content of the hydroxyl-containing monomer in the above-mentioned monomer components is less than 5% by weight, less than 1% by weight, or less than 0.1% by weight.

[0088] In some embodiments, the monomer components constituting the acrylic polymer may include (meth)acrylates containing alicyclic hydrocarbon groups. The amount of (meth)acrylates containing alicyclic hydrocarbon groups used is not particularly limited and can be, for example, 1% or more by weight, or 5% or more by weight of the monomer component. In some embodiments, from the viewpoint of adhesive flexibility, it is appropriate for the content of (meth)acrylates containing alicyclic hydrocarbon groups in the aforementioned monomer component to be 30% or less by weight, preferably 20% or less by weight, or 15% or less by weight, and can be 10% or less by weight. The techniques disclosed herein can preferably be implemented with the content of (meth)acrylates containing alicyclic hydrocarbon groups in the aforementioned monomer component being less than 5% by weight, less than 1% by weight, or less than 0.1% by weight.

[0089] In some methods, it is appropriate to set the content of carboxyl-containing monomers in the monomer composition of the acrylic polymer to be less than 10% by weight, preferably less than 3% by weight or less than 1% by weight (e.g., less than 0.1% by weight). Limiting the amount of carboxyl-containing monomers in this way is advantageous from the viewpoint of avoiding reduced alcohol-removable properties due to excessive hydrophilicity of the adhesive layer. Alternatively, carboxyl-containing monomers may be substantially not used as a monomer composition of the acrylic polymer. Here, "substantially not using carboxyl-containing monomers" means at least not intentionally using carboxyl-containing monomers.

[0090] The composition of the monomer components constituting the aforementioned acrylic polymer can be set such that, based on the composition of these monomer components, the glass transition temperature (Tg) calculated using the Fox formula is -75°C or higher and 10°C or lower. In some embodiments, from the viewpoint of adhesive strength, a Tg of 0°C or lower is appropriate, preferably -10°C or lower, and can be -20°C or lower, -30°C or lower, or -40°C or lower. Furthermore, from the viewpoint of cohesion, the Tg can be, for example, -60°C or higher, -50°C or higher, or -45°C or higher.

[0091] Here, the so-called Fox formula, as shown below, refers to the relationship between the Tg of the copolymer and the glass transition temperature Tgi of the homopolymer obtained by homopolymerizing the monomers constituting the copolymer.

[0092] 1 / Tg = Σ(Wi / Tgi) It should be noted that in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (weight-based copolymerization ratio), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K). The glass transition temperature of the homopolymer used in the calculation of Tg is the value recorded in known sources, specifically the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). If multiple values ​​are recorded in this literature, the highest value is used.

[0093] The adhesive layer in the technology disclosed herein can be formed using an adhesive composition comprising monomeric components as described above, in the form of a polymer, an unpolymerized polymer (i.e., in a form where the polymeric functional groups are unreacted), or a mixture thereof. The adhesive composition can be in various forms, including: an aqueous dispersion adhesive composition in which the adhesive (adhesive component) is dispersed in water; a solvent-based adhesive composition in which the adhesive is contained in an organic solvent; an active energy ray-cured adhesive composition prepared by curing with active energy rays such as ultraviolet light or radiation; a hot-melt adhesive composition formed by coating in a heated molten state and cooling to near room temperature; and so on. Some types of adhesive compositions are solvent-based or solvent-free. Solvent-free adhesive compositions include active energy ray-cured adhesive compositions and hot-melt adhesive compositions. From the viewpoint of ease of controlling alcohol peelability, etc., as the adhesive sheet in the technology disclosed herein, it is preferable to use an adhesive sheet in which the adhesive layer constituting the first adhesive surface is formed from an adhesive layer of a solvent-based adhesive composition or an active energy ray (typically ultraviolet light)-cured adhesive composition.

[0094] During polymerization, known or conventional thermal polymerization initiators and photopolymerization initiators can be used depending on the polymerization method and polymerization mode. There are no particular limitations on thermal polymerization initiators; for example, azo-based polymerization initiators, peroxide-based initiators, redox initiators based on combinations of peroxides and reducing agents, and substituted ethane initiators can be used. There are also no particular limitations on photopolymerization initiators; for example, ketal-based photopolymerization initiators, acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, α-keto alcohol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzoyl-based photopolymerization initiators, thioxanone-based photopolymerization initiators, etc., can be used. One polymerization initiator can be used alone, or two or more can be used in appropriate combinations. The amount of such thermal or photopolymerization initiators used can be the usual amount corresponding to the polymerization method and polymerization mode, without particular limitation. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example about 0.01 to 1 part by weight) of polymerization initiator can be used relative to 100 parts by weight of the monomer to be polymerized.

[0095] In the above polymerization, various known chain transfer agents (also understood as molecular weight regulators or degree of polymerization regulators) can be used as needed. Thiols such as n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoacetic acid, and α-thioglycerol can be used as chain transfer agents. Alternatively, chain transfer agents without sulfur atoms (non-sulfur chain transfer agents) can be used. One chain transfer agent can be used alone, or two or more can be used in combination. When using a chain transfer agent, its amount can be, for example, about 0.01 to 1 part by weight relative to 100 parts by weight of the monomer component. The synthesis of acrylic polymers in the techniques disclosed herein can be suitably carried out even without the use of chain transfer agents.

[0096] The molecular weight of acrylic polymers obtained by appropriately employing the various polymerization methods described above is not particularly limited, and can be set to an appropriate range according to the required properties. The weight-average molecular weight (Mw) of acrylic polymers is, for example, approximately 10 × 10⁻⁶. 4 From the perspective of achieving a good balance between cohesion and adhesion, the value is set to be greater than 30 × 10. 4 This is appropriate. Some types of acrylic polymers preferably have a density of approximately 50 × 10⁻⁶. 4 The above refers to Mw. The upper limit of Mw for acrylic polymers can be approximately 500 × 10⁻⁶. 4 The following (e.g., approximately 150×10) 4 (The following). The above Mw can be approximately 75 × 10. 4 The following is an explanation of Mw, which refers to the value converted from standard polystyrene obtained using gel permeation chromatography (GPC). For example, a GPC apparatus named "HLC-8320GPC" (column: TSKgel GMH-H(S), manufactured by Tosoh Corporation) can be used.

[0097] Some of the adhesive compositions involved can be active energy radiation-cured adhesive compositions. In this specification, "active energy radiation" refers to energy rays possessing the energy to cause chemical reactions such as polymerization, crosslinking, and initiator decomposition. Examples of active energy radiation include ultraviolet light, visible light, infrared light, alpha rays, beta rays, gamma rays, electron rays, neutron rays, and X-rays. As a suitable example of an active energy radiation-cured adhesive composition, a photocurable adhesive composition can be cited. Photocurable adhesive compositions have the advantage that even thick adhesive layers can be easily formed. Ultraviolet-curable adhesive compositions are preferred.

[0098] Typically, the photocurable adhesive composition contains at least a portion (either a portion of the monomer components or a portion of the monomer type) in polymer form. The polymerization method used to form the polymer is not particularly limited, and various conventionally known polymerization methods may be appropriately employed. For example, suitable methods include: thermal polymerization such as solution polymerization, emulsion polymerization, and bulk polymerization (typically carried out in the presence of a thermal polymerization initiator); photopolymerization performed by irradiation with light such as ultraviolet light (typically carried out in the presence of a photopolymerization initiator); radiation polymerization performed by irradiation with radiation such as beta rays and gamma rays; and so on. Photopolymerization is preferred.

[0099] Some preferred embodiments involve photocurable adhesive compositions comprising a partial polymer of monomeric components (e.g., an acrylic partial polymer). Such partial polymers are typically mixtures of polymers derived from monomeric components and unreacted monomers, and preferably exist in a slurry (viscous liquid) state. Hereinafter, this type of partial polymer is sometimes referred to as a "monomer slurry" or simply "slurry." The polymerization method used to partially polymerize the monomeric components is not particularly limited, and various polymerization methods described above can be appropriately selected. From the viewpoint of efficiency and simplicity, photopolymerization is preferred. According to photopolymerization, the polymerization conversion rate (monomer conversion) of the monomeric components can be easily controlled by polymerization conditions such as the amount of light irradiation (light intensity).

[0100] The polymerization conversion rate of the monomer mixture in the aforementioned polymer is not particularly limited. For example, the polymerization conversion rate can be about 70% by weight or less. From the viewpoint of ease of preparation and coatability of the adhesive composition containing the aforementioned polymer, a conversion rate of about 50% by weight or less is suitable, and preferably about 40% by weight or less. The lower limit of the polymerization conversion rate is not particularly limited; typically, a conversion rate of about 1% by weight or more, and about 5% by weight or more, is suitable.

[0101] In adhesive compositions containing the aforementioned polymers, other components (e.g., photopolymerization initiators, crosslinking agents, multifunctional monomers, acrylic oligomers, tackifying resins, silane coupling agents, etc.) may be incorporated as needed. The method of incorporating such other components is not particularly limited; for example, they may be pre-contained in the aforementioned monomer mixture or added to the aforementioned polymers.

[0102] Some of the adhesive compositions involved can be solvent-based adhesive compositions. Solvent-based adhesive compositions typically contain a solution polymer of monomeric components and additives used as needed. The solvent used in solution polymerization (polymerization solvent) can be suitably selected from conventionally known organic solvents (e.g., toluene, ethyl acetate, etc.). According to solution polymerization, a polymerization reaction solution in which the monomeric polymer (typically, the polymerization conversion rate of the monomeric component is 80% by weight or more, preferably 90% by weight or more) is dissolved in the polymerization solvent can be obtained. The solvent-based adhesive compositions disclosed herein are preferably manufactured using the above-described polymerization reaction solution.

[0103] (Multifunctional monomer) Multifunctional monomers can be used in adhesive compositions as needed. Multifunctional monomers help to adjust the cohesive strength of the adhesive, etc. Multifunctional monomers can form cross-linked structures by reacting the aforementioned olefinic unsaturated groups through light irradiation (e.g., ultraviolet light). For example, multifunctional monomers are preferably used as a component in photocurable adhesive compositions. Compounds having two or more olefinic unsaturated groups can be used as multifunctional monomers. One multifunctional monomer can be used alone, or two or more can be used in combination.

[0104] Examples of olefinically unsaturated groups in multifunctional monomers include, but are not limited to, acryloyl, methacryloyl, vinyl, and allyl groups. From the viewpoint of photoreactivity, acryloyl and methacryloyl are preferred olefinically unsaturated groups. Acryloyl is preferred.

[0105] Examples of multifunctional monomers include, for example, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl methacrylate, ethylene methacrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butanediol (meth)acrylate, hexanediol di(meth)acrylate, etc. Suitable examples include trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0106] Regarding the amount of the multifunctional monomer, for example, it is appropriate to set it in the range of about 0.01 parts by weight to 3.0 parts by weight relative to 100 parts by weight of the base polymer (acrylic polymer) or its monomer component. From the viewpoint of achieving a good balance between alcohol exfoliation, disintegration of the bond, and bonding reliability in normal use, in some embodiments, it is appropriate to set the amount of the multifunctional monomer to 2.0 parts by weight or less relative to 100 parts by weight of the base polymer or its monomer component, it is advantageous to set it to 1.5 parts by weight or less, preferably 1.0 parts by weight or less, and it can be 0.7 parts by weight or less, 0.5 parts by weight or less, or 0.3 parts by weight or less.

[0107] (Acrylic oligomers) From the viewpoint of improving cohesion and adhesion, the acrylic adhesives disclosed herein may contain acrylic oligomers. As acrylic oligomers, polymers with a higher Tg than the aforementioned acrylic polymers are preferred. For example, acrylic oligomers are suitable in the case of forming an adhesive (layer) from the adhesive composition using ultraviolet irradiation, as they are less likely to cause polymerization inhibition.

[0108] Suitable examples of acrylic oligomers include, for instance, homopolymers of dicyclopentyl methacrylate (DCPMA), cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBXMA), isobornyl acrylate (IBXA), dicyclopentyl acrylate (DCPA), 1-adamantane methacrylate (ADMA), and 1-adamantane acrylate (ADA), as well as copolymers of DCPMA and methyl methacrylate (MMA), DCPMA and IBXMA, ADA and MMA, CHMA and isobutyl methacrylate (IBMA), CHMA and IBXMA, CHMA and acrylamide morpholine (ACMO), CHMA and diethylacrylamide (DEAA), and CHMA and AA. Acrylic oligomers can be used alone or in combination of two or more.

[0109] The Mw of acrylic oligomers is typically about 1,000 or more and less than about 30,000, preferably about 1,500 or more and less than about 10,000, and more preferably about 2,000 or more and less than about 5,000. When Mw is within the above range, it is easy to appropriately improve the cohesiveness and adhesion to adjacent surfaces. The Mw of acrylic oligomers can be determined by gel permeation chromatography (GPC) and calculated as a value converted to standard polystyrene. Specifically, in an HPLC8020 manufactured by Tosoh Corporation, two TSKgel GMH-H (20) columns were used as columns, and the determination was performed using tetrahydrofuran solvent at a flow rate of about 0.5 mL / min.

[0110] When acrylic adhesives contain acrylic oligomers, their content, relative to 100 parts by weight of the base polymer or its monomer components, can be set to, for example, 0.01 parts by weight or more. From the viewpoint of obtaining better performance, setting it to 0.1 parts by weight or more is advantageous, preferably 0.5 parts by weight or more, and can be set to 1.0 parts by weight or more or 1.5 parts by weight or more. From the viewpoint of adhesive flexibility, compatibility with the base polymer, etc., the content of acrylic oligomers relative to 100 parts by weight of the base polymer or its monomer components is appropriate, for example, less than 30 parts by weight, and can be 20 parts by weight or less, 10 parts by weight or less, or 5 parts by weight or less.

[0111] (Cross-linking agent) The adhesive compositions disclosed herein may contain crosslinking agents as needed. There are no particular limitations on the type of crosslinking agent; it can be selected from conventionally known crosslinking agents, for example, based on the composition of the adhesive composition, in a manner that allows the crosslinking agent to perform an appropriate crosslinking function within the adhesive. Examples of usable crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, carbodiimide-based crosslinking agents, melamine-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, hydrazine-based crosslinking agents, amine-based crosslinking agents, etc. These can be used alone or in combination of two or more.

[0112] The content of the crosslinking agent (or its total amount if two or more crosslinking agents are included) is not particularly limited. From the viewpoint of achieving a well-balanced adhesive with good adhesive properties such as bonding strength and cohesion, it is appropriate for the amount of crosslinking agent to be about 5 parts by weight or less relative to 100 parts by weight of the acrylic polymer or the monomer components constituting the acrylic polymer, preferably about 0.001 to 5 parts by weight, more preferably about 0.001 to 4 parts by weight, and even more preferably about 0.001 to 3 parts by weight. Alternatively, an adhesive composition may be used that does not contain such a crosslinking agent. For example, when using a photocurable adhesive composition as the adhesive composition disclosed herein, the adhesive composition may substantially not contain crosslinking agents such as isocyanate-based crosslinking agents. Here, "the adhesive composition substantially does not contain crosslinking agents (typically isocyanate-based crosslinking agents)" means that the amount of crosslinking agent relative to 100 parts by weight of the monomer components is less than 0.05 parts by weight (e.g., less than 0.01 parts by weight).

[0113] To make the crosslinking reaction proceed more efficiently, a crosslinking catalyst may also be used. Additionally, the adhesive composition used to form the adhesive may contain a crosslinking inhibitor (e.g., a compound that produces a keto-enol tautomer). The amount of crosslinking catalyst and crosslinking inhibitor used is not limited to a specific range and can be used in appropriate amounts depending on the purpose, etc.

[0114] [Polyester-based adhesives] In some other aspects of the technology disclosed herein, an adhesive comprising a polyester polymer may be preferably used as the constituent material of the adhesive layer.

[0115] (Polyester polymer) Polyester polymers are typically included as the base polymer in the adhesive layer. In this specification, polyester polymers refer to polymers obtained by polycondensation of polycarboxylic acids and polyols.

[0116] As polycarboxylic acids used in the synthesis of the aforementioned polyester polymers, aromatic polycarboxylic acids, alicyclic polycarboxylic acids, aliphatic polycarboxylic acids, and unsaturated polycarboxylic acids can all be used. Dicarboxylic acids containing two carboxyl groups per molecule, tricarboxylic acids containing three carboxyl groups (tricarboxylic acids), and polycarboxylic acids containing four or more carboxyl groups (quadrivalent or higher) can all be used.

[0117] Specific examples of polycarboxylic acids include: isophthalic acid, terephthalic acid, phthalic acid, benzylmalonic acid, 2,2'-biphenyl dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-dicarboxylic acid diphenyl ether, naphthalenedicarboxylic acid, and other aromatic dicarboxylic acids; 1,2-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, norbornanedicarboxylic acid, adamantanedicarboxylic acid, and other alicyclic dicarboxylic acids; malonic acid, Aliphatic dicarboxylic acids such as succinic acid, glutaric acid, dimethylglutaric acid, adipic acid, trimethyl adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, thiodipropionic acid, and diethanolic acid; unsaturated dicarboxylic acids such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, and citraconic acid; polycarboxylic acids with three or more tertiary components such as trimellitic acid, pyromellitic acid, adamantane tricarboxylic acid, and pyromellitic acid; dimer acids and trimer acids obtained by dimerizing or trimerizing fatty acids such as oleic acid; their derivatives; etc. These can be used individually or in combination of two or more. It should be noted that the derivatives of the above polycarboxylic acids include carboxylates, carboxylic anhydrides, carboxylic halides, and carboxylic esters.

[0118] As a polycarboxylic acid, aromatic polycarboxylic acids (typically aromatic dicarboxylic acids) are preferred. Using aromatic polycarboxylic acids tends to easily prevent the penetration of polar chemicals, etc. Furthermore, there is a tendency to improve the cohesive strength and holding power of the adhesive. Preferred examples include isophthalic acid, terephthalic acid, and phthalic acid, with isophthalic acid being more preferred. These can be used alone or in combination of two or more. For example, the combined use of isophthalic acid and terephthalic acid can be cited.

[0119] The molar percentage of aromatic carboxylic acids in the total molar number of polycarboxylic acids in the monomer component of polyester polymers is not particularly limited, but it is appropriate to set it to about 1 mol% or more. From the viewpoint of durability and holding power against polar chemicals, it is preferably about 10 mol% or more, more preferably about 30 mol% or more, and even more preferably about 40 mol% or more. For example, it can be about 50 mol% or more, or about 60 mol% or more. In addition, it is appropriate to set the above-mentioned molar percentage of aromatic carboxylic acids to be about 95 mol% or less. From the viewpoint of adhesive properties such as peel strength, it is preferably about 85 mol% or less, more preferably about 80 mol% or less, and even more preferably about 75 mol% or less (e.g., 70 mol% or less). The above-mentioned molar percentage of aromatic carboxylic acids can be about 65 mol% or less (e.g., about 55 mol% or less).

[0120] In addition, aliphatic polycarboxylic acids (typically aliphatic dicarboxylic acids) are preferred as polycarboxylic acids. Suitable examples include dimethylglutaric acid, adipic acid, trimethyl adipic acid, pimelic acid, octanoic acid, azelaic acid, and sebacic acid, among which adipic acid, pimelic acid, octanoic acid, azelaic acid, and sebacic acid are more preferred, and adipic acid and sebacic acid are even more preferred.

[0121] The molar percentage of aliphatic carboxylic acids in the total molar number of polycarboxylic acids in the monomer component of polyester polymers is not particularly limited, but it is appropriate to set it to about 1 mol% or more. From the viewpoint of adhesive properties such as peel strength, it is preferably about 10 mol% or more, more preferably about 15 mol% or more, even more preferably about 20 mol% or more, particularly preferably about 25 mol% or more, and can be about 35 mol% or more (e.g., about 50 mol% or more). In addition, it is appropriate to set the above-mentioned molar percentage of aliphatic carboxylic acids to about 90 mol% or less. From the viewpoint of durability against polar chemicals, it is preferably about 70 mol% or less, more preferably about 60 mol% or less, and can be about 50 mol% or less, or about 40 mol% or less.

[0122] From the viewpoint of obtaining a suitable glass transition temperature (Tg) for the adhesive, it is preferable to use aliphatic polycarboxylic acids (typically aliphatic dicarboxylic acids) and aromatic polycarboxylic acids (typically aromatic dicarboxylic acids). Aliphatic polycarboxylic acids C A With aromatic polycarboxylic acids C B molar ratio (C) A :C B Setting the molar ratio to approximately 1:49 to 49:1 is appropriate, and it can be approximately 5:45 to 45:5. In a preferred embodiment, the molar ratio (C...) A :C B The ratio is approximately 5:45 to 40:10, more preferably approximately 10:40 to 35:15 (e.g., approximately 15:35 to 30:20), for example approximately 5:45 to 25:25, or approximately 10:40 to 20:30 (e.g., approximately 15:35 to 20:30).

[0123] Furthermore, the polycarboxylic acid is preferably composed mainly of dicarboxylic acids. In some embodiments, it is appropriate for the proportion of dicarboxylic acids in the total amount of polycarboxylic acids in the monomer component of the polyester polymer to be about 90 mol% or more, preferably about 95 mol% or more, more preferably about 98 mol% or more, and even more preferably about 99 mol% or more (e.g., 99 to 100 mol%), typically 99.9 mol% or more (in other words, the polycarboxylic acid is substantially composed of dicarboxylic acids). It is appropriate for the proportion of ternary or more polycarboxylic acids in the total amount of the aforementioned polycarboxylic acids to be about 10 mol% or less, preferably about 5 mol% or less, more preferably about 3 mol% or less, even more preferably about 1 mol% or less, and particularly preferably about 0.1 mol% or less (in other words, the polycarboxylic acid substantially does not contain ternary or more polycarboxylic acids).

[0124] Aliphatic polyols, alicyclic polyols, aromatic polyols, and unsaturated polyols can all be used as polyols in the synthesis of the polyester polymers disclosed herein. Diols containing two hydroxyl groups per molecule, triols containing three hydroxyl groups, and polyols with four or more hydroxyl groups can all be used.

[0125] Specific examples of the aforementioned polyols include, for instance: ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2-methyl-1,3-hexanediol, 2,2,4-trimethyl-1,6-hexanediol, 1,8-octanediol, and other aliphatic diols; 1,2-cyclohexanediol, 1,3- Cyclohexanediol, 1,4-cyclohexanediol, spiroglycol, tricyclodecanediol, adamantanediol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and other alicyclic diols; 4,4'-thiodiphenol, 4,4'-methylenediphenol, 4,4'-dihydroxybiphenyl, catechol, resorcinol and hydroquinone, 2,5-naphthalenediol, p-xylenediol and their ethylene oxide and propylene oxide adducts, and other aromatic diols; dimerized diols; pentaerythritol, dipentaerythritol, tripentaerythritol, glycerol, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, adamantanetriol, and other polyols with three or more tertiary components; etc. These can be used individually or in combination of two or more.

[0126] As polyols, aliphatic polyols (typically aliphatic diols) and alicyclic polyols (typically alicyclic diols) are preferred, and aliphatic polyols are more preferred. By synthesizing these polyols (preferably aliphatic diols) in combination with the aforementioned polycarboxylic acids (preferably polycarboxylic acids containing aromatic dicarboxylic acids), polyester polymers with excellent adhesive properties can preferably be obtained. Suitable examples include ethylene glycol, propylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol. From the viewpoint of reactivity, ethylene glycol, 1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol are more preferred. These can be used alone or in combination of two or more. For example, combinations of ethylene glycol, 2,2-dimethyl-1,3-propanediol and 1,6-hexanediol can be cited.

[0127] The molar percentage (preferably the molar percentage of aliphatic and alicyclic polyols) of the total molar number of polyols in the monomer component of the polyester polymer is not particularly limited, but is appropriately set to about 50 mol% or more. From the viewpoint of obtaining good adhesive properties, it is preferably about 70 mol% or more, more preferably about 80 mol% or more, further preferably about 90 mol% or more, and particularly preferably about 95 mol% or more (e.g., 99 to 100 mol%). In addition, the above-mentioned molar percentage (preferably the molar percentage of aliphatic polyols) can, for example, be about 95 mol% or less.

[0128] Furthermore, the polyols are preferably composed primarily of diols. In some embodiments, it is appropriate for the proportion of diols in the total amount of polyols in the monomer component of the polyester polymer to be about 90 mol% or more, preferably about 95 mol% or more, more preferably about 98 mol% or more, even more preferably about 99 mol% or more (e.g., 99 to 100 mol%), and typically 99.9 mol% or more (in other words, the polyols are substantially composed of diols). It is appropriate for the proportion of trivalent or higher polyols in the total amount of the aforementioned polyols to be about 10 mol% or less, preferably about 5 mol% or less, more preferably about 3 mol% or less, even more preferably about 1 mol% or less, and particularly preferably about 0.1 mol% or less (in other words, the polyols substantially do not contain trivalent or higher polyols).

[0129] It should be noted that although polyester polymers can be substantially composed of the aforementioned polycarboxylic acids and polyols, other copolymer components (e.g., monocarboxylic acids and alcohols) besides polycarboxylic acids and polyols can also be copolymerized for purposes such as introducing desired functional groups and adjusting molecular weight, without impairing the effects of the technology disclosed herein. The proportion of these other copolymer components is appropriately set, for example, to be less than 3 mol%, typically to be less than 1 mol% (further, less than 0.1 mol%). The technology disclosed herein can also preferably be implemented in a manner where the monomer composition of the polyester polymer substantially does not contain the aforementioned other copolymer components.

[0130] The method for obtaining the polyester polymers disclosed herein is not particularly limited, and polymerization methods known as methods for synthesizing polyester polymers can be appropriately employed. From the viewpoint of polymerization efficiency, molecular weight control, etc., it is appropriate to combine the monomer raw materials used in the synthesis of polyester polymers in such a manner that the polyol constitutes more than one equivalent (e.g., 1 to 2 equivalents) relative to one equivalent of the polycarboxylic acid. In a preferred embodiment, the amount of polyol is greater than one equivalent and less than 1.8 equivalents (e.g., 1.2 to 1.7 equivalents) relative to one equivalent of the polycarboxylic acid.

[0131] Regarding the polyester polymers disclosed herein, they can be obtained, similarly to conventional polyesters, through the polycondensation of polycarboxylic acids and polyols. More specifically, polyester polymers can be synthesized by reacting the carboxyl groups of the polycarboxylic acid with the hydroxyl groups of the polyol. Typically, the reaction can be carried out while removing the water (generated water) produced in the above reaction from the reaction system. Methods for removing the generated water from the reaction system include blowing an inert gas into the reaction system and removing the generated water along with the inert gas, or distilling the generated water from the reaction system under reduced pressure (reduced pressure method). From the perspective of easily shortening the synthesis time and improving productivity, the reduced pressure method is preferred.

[0132] The reaction temperature and the pressure within the reaction system (when using a reduced pressure method) for the above reactions (including esterification and polycondensation) can be appropriately set to efficiently obtain polyester polymers with the target properties (e.g., molecular weight). While not particularly limited, a reaction temperature of 180°C to 260°C is generally suitable, for example, 200°C to 220°C. Setting the reaction temperature within this range allows for a good reaction rate, increases productivity, and easily prevents or inhibits the deterioration of the resulting polyester polymer. While not particularly limited, a pressure below 10 kPa (typically 10 kPa to 0.1 kPa) is generally suitable, for example, 4 kPa to 0.1 kPa. Setting the pressure within the reaction system within this range allows for efficient distillation removal of water generated during the reaction, easily maintaining a good reaction rate. Furthermore, at higher reaction temperatures, setting the pressure within the reaction system above the lower limit above easily prevents the distillation removal of the polycarboxylic acids and polyols used as raw materials. From the perspective of maintaining stable pressure within the reaction system, it is generally appropriate to set the pressure within the reaction system to be above 0.1 kPa.

[0133] Similar to the synthesis of conventional polyesters, suitable known or conventional catalysts can be used in the above reactions for esterification and condensation purposes. Examples of such catalysts include various metal compounds such as titanium-based, germanium-based, antimony-based, tin-based, and zinc-based compounds; strong acids such as p-toluenesulfonic acid and sulfuric acid; and so on. Titanium-based metal compounds (titanium compounds) are preferred. Specific examples of such titanium compounds include tetraalkoxytitanium such as tetrabutoxytitanium, tetraisopropoxytitanium, tetrapropoxytitanium, and tetraethoxytitanium; alkyl titanate esters such as tetraisopropyl titanate, tetrabutyl titanate, octaalkyl trititanate, and hexaalkyl distitanate; and titanium acetate.

[0134] In the above process of synthesizing polyester polymers via the reaction of polycarboxylic acids and polyols, a solvent may or may not be used. The above synthesis can be carried out substantially without the use of organic solvents (meaning, for example, excluding the intentional use of organic solvents as reaction solvents in the above reactions). This method of synthesizing polyester polymers substantially without the use of organic solvents, and of using these polyester polymers to prepare polyester adhesives, meets the requirement of controlling the use of organic solvents during their manufacturing process and is therefore preferred.

[0135] It should be noted that, in the above reactions, there is generally a correlation between the molecular weight of the synthesized polyester polymer and the viscosity of the reaction system. Therefore, this can be used to manage the molecular weight of the polyester polymer. For example, by continuously or intermittently measuring (monitoring) the torque of the stirrer and the viscosity of the reaction system during the reaction, polyester polymers that meet the target molecular weight can be synthesized with high precision.

[0136] While not specifically limited, in some methods, polyester polymers with a hydroxyl value of less than 30 mg KOH / g (e.g., less than 15 mg KOH / g) can be used as the base polymer for polyester adhesives. Preferably, the hydroxyl value of the polyester polymer is less than 12 mg KOH / g, more preferably less than 10 mg KOH / g, and for example, less than 8 mg KOH / g or less than 5 mg KOH / g. The lower limit of the aforementioned hydroxyl value is 0 mg KOH / g or higher (typically greater than 0 mg KOH / g, for example, 1 mg KOH / g or higher). The hydroxyl value of the polyester polymer can be determined according to JIS K0070:1992. If a nominal hydroxyl value is provided by the manufacturer, this value can be used.

[0137] Furthermore, although not specifically limited, in some methods, polyester polymers with an acid value of less than 10 mg KOH / g can be used as the base polymer for polyester adhesives. The acid value of the polyester polymer is preferably less than 5 mg KOH / g, more preferably less than 3 mg KOH / g, and even more preferably less than 2 mg KOH / g, for example, less than 1 mg KOH / g. The lower limit of the above acid value is 0 mg KOH / g. The hydroxyl value of the polyester polymer can be 0 mg KOH / g or greater than 0 mg KOH / g. The acid value of the polyester polymer can be determined according to JIS K0070:1992. If the nominal value of the hydroxyl value is provided by the manufacturer, etc., that value can be used.

[0138] While not particularly limited, from the viewpoint of the reliability of the bonding between the adhesive sheet and the adherend, it is advantageous for the polyester polymer to have a Tg of about 15°C or less, preferably about 0°C or less, more preferably about -10°C or less, and even more preferably about -15°C or less, for example, about -20°C or less. From the viewpoint of the cohesive strength of the adhesive layer, the Tg of the polyester polymer is generally about -80°C or more, preferably about -60°C or more, more preferably about -40°C or more, and even more preferably about -30°C or more (e.g., about -20°C or more). The Tg of the polyester polymer can be adjusted by appropriately changing the monomer composition (i.e., the type and proportion of monomers used in the synthesis of the polymer). In the technology disclosed herein, the base polymers used as the adhesive layer can be high-Tg polyester polymers (e.g., Tg above -20°C, typically Tg between -20°C and 15°C), medium-Tg polyester polymers (e.g., Tg above -40°C and below -20°C), and low-Tg polyester polymers (e.g., Tg below -40°C, typically above -80°C and below -40°C). Among these, medium-Tg and high-Tg polyester polymers are preferred.

[0139] The temperature glycemic index (Tg) of polyester polymers can be measured using a commercially available differential scanning calorimeter (e.g., TA Instruments, model "DSC Q20"). The measurement conditions are a shear strain at a frequency of 1 Hz, a temperature range of -90°C to 100°C, and a heating rate of 10°C / min. If the manufacturer provides the nominal hydroxyl value, this value can be used.

[0140] The number-average molecular weight (Mn) of polyester polymers is not particularly limited, and can be, for example, approximately 5000 or more. Here, Mn refers to the value converted from standard polystyrene obtained using GPC (gel permeation chromatography). For example, a GPC apparatus named "HLC-8320GPC" (column: TSKgel GMH-H(S), manufactured by Tosoh Corporation) can be used. From the viewpoint of durability, cohesive strength, and holding power for polar chemicals, the Mn of polyester polymers is preferably approximately 7000 or more, more preferably approximately 9000 or more, and can be, for example, approximately 12000 or more, approximately 15000 or more, or approximately 18000 or more (for example, approximately 24000 or more). The Mn of polyester polymers is typically approximately 10 × 10⁻⁶. 4 The following is appropriate, preferably about 5 × 10 from the viewpoint of, for example, adhesive strength. 4 Hereinafter, approximately 3 × 10 is preferred. 4 The following can be, for example, approximately 2 × 10 4 The following can be approximately 1.5 × 10 4the following.

[0141] (Cross-linking agent) The adhesive composition used to form a polyester-based adhesive layer preferably contains a crosslinking agent as an optional component. The adhesive layer disclosed herein may contain the aforementioned crosslinking agent in the form of a post-crosslinking reaction, a pre-crosslinking reaction, a partially crosslinked reaction, an intermediate form, or a composite form thereof. The aforementioned crosslinking agent is typically contained primarily in the adhesive layer in the post-crosslinking reaction form. It should be noted that the crosslinking agent used for crosslinking polyester polymers can also function as a chain extender.

[0142] There are no particular restrictions on the type of crosslinking agent; it can be appropriately selected from existing known crosslinking agents. Examples of such crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, and metal chelate-based crosslinking agents. A single crosslinking agent can be used, or two or more can be used in combination. Isocyanate-based crosslinking agents are preferred.

[0143] As isocyanate-based crosslinking agents, polyfunctional isocyanates (compounds having an average of more than two isocyanate groups per molecule, including compounds with isocyanurate structures) are preferred. Isocyanate-based crosslinking agents can be used alone or in combination of two or more.

[0144] Examples of polyfunctional isocyanates include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates.

[0145] Specific examples of aliphatic polyisocyanates include 1,2-ethylene diisocyanate; tetramethylene diisocyanates such as 1,2-tetramethylene diisocyanate, 1,3-tetramethylene diisocyanate, and 1,4-tetramethylene diisocyanate; hexamethylene diisocyanates such as 1,2-hexamethylene diisocyanate, 1,3-hexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, 1,5-hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,5-hexamethylene diisocyanate; 2-methyl-1,5-pentanediisocyanate, 3-methyl-1,5-pentanediisocyanate, and lysine diisocyanate.

[0146] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated diphenylmethylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and so on.

[0147] Specific examples of aromatic polyisocyanates include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenyl ether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, and 2,2'-diphenylpropane-4,4'-diisocyanate. Cyanates, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, terephthalene diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, phenylenediamine-1,4-diisocyanate, phenylenediamine-1,3-diisocyanate, etc.

[0148] As a preferred polyfunctional isocyanate, examples include polyfunctional isocyanates having an average of three or more isocyanate groups per molecule. This isocyanate with three or more functions can be a polymer (e.g., a dimer or trimer) of a difunctional or trifunctional or more functional isocyanate, a derivative (e.g., an addition reaction product of a polyol with two or more molecules of a polyfunctional isocyanate), a polymer, etc. Examples include dimers and / or trimers of diphenylmethane diisocyanate, isocyanurates of hexamethylene diisocyanate (trimeric adducts of the isocyanurate structure), reaction products of trimethylolpropane and toluene diisocyanate, reaction products of trimethylolpropane and hexamethylene diisocyanate, polymethylene polyphenyl isocyanates, polyether polyisocyanates, polyester polyisocyanates, and other polyfunctional isocyanates. Commercially available products of this multifunctional isocyanate include, for example, "DURANATE TPA-100" manufactured by Asahi Kasei Chemicals Co., Ltd.; "CORONATE L", "CORONATE HL", "CORONATE HK", "CORONATE HX", and "CORONATE 2096" manufactured by Tosoh Co., Ltd.; and "TAKENATE D110N", "TAKENATE D120N", "TAKENATE D140N", and "TAKENATE D160N" manufactured by Mitsui Chemicals Co., Ltd.

[0149] In the use of isocyanate-based crosslinking agents, the amount is not particularly limited. The amount of isocyanate-based crosslinking agent can be, for example, about 0.5 parts by weight or more and about 10 parts by weight or less relative to 100 parts by weight of the polyester polymer. From the viewpoint of durability against polar chemicals, it is generally appropriate to set the amount of isocyanate-based crosslinking agent to about 1 part by weight or more relative to 100 parts by weight of the polyester polymer, and preferably to set it to about 1.5 parts by weight or more (e.g., about 3 parts by weight or more). Furthermore, it is generally appropriate to set the amount of isocyanate-based crosslinking agent to about 8 parts by weight or less relative to 100 parts by weight of the polyester polymer, and preferably to set it to about 5 parts by weight or less.

[0150] The total amount of crosslinking agent is not particularly limited. For example, it can be selected from about 0.005 parts by weight or more (e.g., 0.01 parts by weight or more, typically 0.1 parts by weight or more) to about 10 parts by weight or less (e.g., about 8 parts by weight or less, preferably about 5 parts by weight or less) relative to 100 parts by weight of the base polymer.

[0151] (Cross-linking catalyst) To make the crosslinking reaction more efficient, in addition to the crosslinking agents mentioned above, crosslinking catalysts can also be used. Examples of crosslinking catalysts include zirconium-containing compounds such as zirconium tetraacetylacetonate, zirconium monoacetylacetonate, zirconium ethyl acetoacetate, and zirconium octanoate compounds (zirconium-based catalysts); tin-containing compounds such as dioctyltin dilaurate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diacetylacetonate, tetra-n-butyltin, trimethyltin hydroxide, and butyltin oxide (tin-based catalysts); aluminum-containing compounds such as aluminum sec-butoxide, aluminum triacetylacetonate, aluminum diacetate, and aluminum triacetate (aluminum-based catalysts); iron-containing compounds such as iron acetylacetonate (iron-based catalysts); titanium-containing compounds such as tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetraoctyl titanate, titanium acetylacetonate, titanium tetraacetylacetonate, and titanium ethyl acetoacetate (titanium-based catalysts); and organometallic catalysts. A single crosslinking catalyst can be used, or two or more can be used in combination.

[0152] There is no particular limitation on the amount of crosslinking catalyst used. Relative to 100 parts by weight of the polyester polymer, the amount of crosslinking catalyst can be, for example, about 0.001 parts by weight or more, preferably about 0.01 parts by weight or more, or about 0.05 parts by weight or more (e.g., 0.10 parts by weight or more). Furthermore, relative to 100 parts by weight of the polyester polymer, the amount of crosslinking catalyst can be, for example, about 3 parts by weight or less, preferably about 1 part by weight or less, or about 0.3 parts by weight or less.

[0153] (Hydrolysis resistant agent) The adhesive composition used in the formation of polyester adhesive layers may contain a hydrolysis-resistant agent (also known as a hydrolysis-resistant agent). By adding a hydrolysis-resistant agent, the hydrolysis reaction in the adhesive is suppressed, easily resulting in good durability of the adhesive properties. There are no particular limitations on the hydrolysis-resistant agent; known or conventional hydrolysis-resistant agents can be used. Examples include compounds containing oxazoline groups, compounds containing epoxy groups, and compounds containing carbodiimide groups. Among these, compounds containing carbodiimide groups are preferred. A single hydrolysis-resistant agent may be used, or two or more may be used in combination.

[0154] Examples of compounds containing a carbodiimide group include dicyclohexylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, diphenylcarbodiimide, ditert-butylcarbodiimide, di-β-naphthylcarbodiimide, and monofunctional cyclic carbodiimide. Here, a monofunctional cyclic carbodiimide refers to a compound having one carbodiimide group in its molecular structure, obtained by bonding the first nitrogen atom of the carbodiimide group to the second nitrogen atom using a bonding group consisting of an aliphatic group, an alicyclic group, an aromatic group, or a combination thereof. It should be noted that the aforementioned bonding group may include heteroatoms or substituents. Suitable examples of compounds containing a carbodiimide group include dicyclohexylcarbodiimide, diisopropylcarbodiimide, and monofunctional cyclic carbodiimide.

[0155] The amount of the hydrolysis-resistant agent (suitably a carbodiimide-containing compound) is not particularly limited. However, to preferably exhibit the effect of containing the hydrolysis-resistant agent, it is suitable to set it to about 0.05 parts by weight or more relative to 100 parts by weight of the polyester polymer, preferably about 0.1 parts by weight or more, and for example, about 0.3 parts by weight or more. Regarding the upper limit of the above-mentioned amount of the hydrolysis-resistant agent, for example, it is suitable to be about 5 parts by weight or less relative to 100 parts by weight of the polyester polymer, preferably about 3 parts by weight or less, and for example, 1 part by weight or less.

[0156] [Other ingredients] (Adhesive resin) The adhesives disclosed herein (e.g., acrylic adhesives, polyester adhesives, etc.) may also include tackifying resins. Examples of tackifying resins include rosin-based tackifying resins, rosin derivative tackifying resins, petroleum-based tackifying resins, terpene-based tackifying resins, phenolic tackifying resins, and ketone-based tackifying resins. These can be used individually or in combination of two or more. Preferably, one or more selected from rosin-based tackifying resins, rosin derivative tackifying resins, and terpene phenolic resins are used. For example, a tackifying resin with a softening point of 80°C or higher (e.g., 120°C or higher and 180°C or lower) is preferred (rosin derivative tackifying resins are suitable).

[0157] Regarding the amount of tackifying resin used, from the viewpoint of maximizing its effectiveness, it is appropriate to use 1 part by weight or more relative to 100 parts by weight of the monomer component of the base polymer constituting the adhesive. From the viewpoint of achieving even better performance, it can be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, or 25 parts by weight or more. Furthermore, the amount of tackifying resin relative to 100 parts by weight of the monomer component can be, for example, 50 parts by weight or less, or 30 parts by weight or less. In the adhesives disclosed herein, the amount of tackifying resin relative to 100 parts by weight of the monomer component can be less than 1 part by weight, or it can be substantially free of tackifying resin.

[0158] (surfactant) Adhesives may contain surfactants. Known nonionic surfactants, anionic surfactants, cationic surfactants, etc., can be used as surfactants. Nonionic surfactants are preferred. A single surfactant may be used, or two or more may be used in combination.

[0159] Examples of nonionic surfactants include: polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene hexadecyl ether, polyoxyethylene stearyl ether, and polyoxyethylene oil-based ether; polyoxyethylene alkylphenyl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, and sorbitan monooleate; polyoxyethylene fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan triisostearate, polyoxyethylene sorbitan monooleate, and polyoxyethylene sorbitan trioleate; polyoxyethylene glycerol ether fatty acid esters; polyoxyethylene-polyoxypropylene block copolymers; and so on.

[0160] Examples of anionic surfactants include: alkyl sulfates such as lauryl sulfate and octadecyl sulfate; fatty acid salts; alkylbenzene sulfonates such as nonylbenzene sulfonate and dodecylbenzene sulfonate; naphthalene sulfonates such as dodecylnaphthalene sulfonate; alkyl diphenyl ether disulfonates such as dodecyl diphenyl ether disulfonate; polyoxyethylene alkyl ether sulfates such as polyoxyethylene octadecyl ether sulfate and polyoxyethylene lauryl ether sulfate; polyoxyethylene alkyl phenyl ether sulfates such as polyoxyethylene lauryl phenyl ether sulfate; polyoxyethylene styrene phenyl ether sulfate; sulfosuccinates such as lauryl sulfosuccinate and polyoxyethylene lauryl sulfosuccinate; polyoxyethylene alkyl ether phosphates; polyoxyethylene alkyl ether acetates; and so on. When anionic surfactants form salts, these salts can be, for example, metal salts (preferably monovalent metal salts) such as sodium salts, potassium salts, calcium salts, and magnesium salts, ammonium salts, and amine salts.

[0161] The content of surfactant in the adhesive is not particularly limited and can be set in a way that allows the surfactant to exert its desired effect. In some embodiments, the surfactant content may be, for example, 0.05 parts by weight or more, or 0.1 parts by weight or more, 0.5 parts by weight or more, 1.0 parts by weight or more, or 1.5 parts by weight or more, relative to 100 parts by weight of the monomer components constituting the base polymer. In other embodiments, it is appropriate to set the amount of surfactant to 3 parts by weight or less relative to 100 parts by weight of the monomer components constituting the base polymer, preferably 2 parts by weight or less, more preferably less than 1 part by weight or less than 0.5 parts by weight. The technology disclosed herein can preferably be implemented such that the surfactant content in the adhesive is limited to less than 0.3 parts by weight (i.e., 0 parts by weight or more and less than 0.3 parts by weight), less than 0.1 parts by weight, or less than 0.01 parts by weight relative to 100 parts by weight of the monomer components constituting the base polymer, or the adhesive is substantially free of surfactant.

[0162] (Other optional ingredients) The adhesives disclosed herein may include, as needed, various general additives in the field of adhesives as optional components, such as viscosity modifiers (e.g., tackifiers), pH adjusters, leveling agents, plasticizers, silane coupling agents, fillers, colorants such as pigments and / or dyes, stabilizers, preservatives, and anti-aging agents. Regarding such various additives, conventionally known substances can be used using conventional methods; detailed descriptions are omitted as they do not specifically characterize this invention.

[0163] In some embodiments, the adhesive constituting the first adhesive layer can be an adhesive in which the amount of components other than the base polymer (e.g., an acrylic polymer) is limited. It is suitable, for example, to have an amount of components other than the base polymer of the adhesive of less than 30% by weight, preferably less than 15%, 12%, or 10% by weight. Adhesives in which the amount of components other than the base polymer is limited readily meet specified optical properties (e.g., transparency) and can become suitable for optical applications. In some embodiments, the amount of components other than the base polymer in the adhesive can be less than 5% by weight, less than 3% by weight, or less than 2% by weight. For example, in adhesives formed from photocurable adhesive compositions, a configuration in which the amount of components other than the base polymer is limited is preferred.

[0164] [Formation of the adhesive layer] The adhesive layer of the adhesive sheet disclosed herein can be a cured layer of the adhesive composition. That is, the adhesive layer can be formed by applying (e.g., coating) the adhesive composition to a suitable surface and then performing a curing treatment. In the case of an adhesive composition using a monomeric component of a partial polymer (acrylic polymer slurry), typically, as the above-mentioned curing treatment, a final copolymerization reaction is carried out. That is, a portion of the polymer is fed to a further copolymerization reaction to form a complete polymer. When two or more curing treatments (drying, crosslinking, polymerization, etc.) are performed, they can be carried out simultaneously or in multiple stages. For example, in cases where drying is required in the form of a photocurable adhesive composition (e.g., a photocurable adhesive composition in the form of a monomeric component of a partial polymer dissolved in an organic solvent), photocuring can be performed after the composition is dried. In the case of solvent-based adhesive compositions or water-dispersible adhesive compositions, the above-mentioned curing treatment typically includes drying (heat drying), and further treatments such as crosslinking can be performed as needed.

[0165] The coating of the adhesive composition can be carried out using conventional coating machines such as gravure roller coaters, reverse roller coaters, kiss roller coaters, dip roller coaters, bar coaters, doctor blade coaters, and spray coaters.

[0166] [Thickness of adhesive layer] The thickness of the adhesive layer is not particularly limited and can be, for example, around 3 μm to 2000 μm. From the viewpoint of step followability and adhesion to the adhered object, in some embodiments, an adhesive layer thickness of 5 μm or more is advantageous, preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more. Furthermore, from the viewpoint of preventing adhesive residue due to cohesive failure of the adhesive layer, in some embodiments, the adhesive layer thickness is typically 500 μm or less, preferably 200 μm or less, even more preferably 100 μm or less, and can be 50 μm or less, or even 30 μm or less.

[0167] [First adhesive layer and second adhesive layer] The adhesive sheet disclosed herein is in the form of having a first adhesive layer and a second adhesive layer (for example, a double-sided adhesive sheet with a substrate having a first adhesive layer on the first side of the substrate and a second adhesive layer on the second side of the substrate). In this case, the adhesive constituting the first adhesive layer (first adhesive) and the adhesive constituting the second adhesive layer (second adhesive) can have the same composition or different compositions. Furthermore, the composition (thickness, etc.) and various properties of the first adhesive layer can be the same as or different from those of the second adhesive layer. For example, the reduction rate R of the peel force relative to the first adhesive layer... A Regarding the peel force reduction rate R of the second adhesive layer A The degree can be the same, higher, or lower (e.g., less than 70%, less than 50%, etc.). From the viewpoint of ease of manufacturing the adhesive sheet, it is preferable to use the same adhesive composition to form the first adhesive layer and the second adhesive layer in some embodiments. Furthermore, the thickness of the second adhesive layer can be greater, less, or the same as the thickness of the first adhesive layer. In some embodiments, it is preferable that the thicknesses of the first adhesive layer and the second adhesive layer are the same.

[0168] <Substrate> The adhesive sheet disclosed herein can be composed of a substrate. Examples of substrates include various resin films such as polyolefin films, polyester films, and polyvinyl chloride films; foam sheets formed from foams such as polyurethane foam, polyethylene foam, and polychloroprene foam; fabrics and nonwovens obtained individually or through blending of various fibrous materials (such as natural fibers like hemp and cotton, synthetic fibers like polyester and vinylon, and semi-synthetic fibers like acetate); fibrous aggregates such as paper (washi paper, premium paper, kraft paper, and crepe paper); metal foils such as aluminum foil, copper foil, and stainless steel (SUS); and so on. It can also be a substrate for a structure formed by combining these materials. Examples of substrates for composite structures include, for instance, laminated substrates (multilayer structure substrates) formed by stacking metal foil with the aforementioned resin films, and resin sheets reinforced with inorganic fibers such as glass cloth.

[0169] In some methods, a material comprising a self-supporting or shape-independent resin film as the base film is preferably used as the substrate. Here, "resin film" refers to a non-porous structure, typically a substantially bubble-free (pore-free) resin film. Therefore, the resin film described above is a concept distinct from foamed films and nonwoven fabrics. The resin film can be a single-layer structure or a multi-layer structure with two or more layers (e.g., a three-layer structure). The resin film can be a transparent film. Transparent resin films are suitable for optical applications.

[0170] Suitable examples of resin materials constituting resin films include polyester resins, polyphenylene sulfide (PPS) resins, polyolefin resins, and polyimide resins. Specific examples of resin films preferably used as a substrate layer include polyethylene terephthalate (PET) films, polyethylene naphthalate (PEN) films, PPS films, polyetheretherketone (PEEK) films, transparent polyimide (CPI) films, polypropylene (PP) films, and cellulose triacetate (TAC) films. Examples preferred from a strength perspective include PET films, PEN films, PPS films, PEEK films, and CPI films. Examples preferred from the viewpoints of ease of acquisition, dimensional stability, and optical properties include PET films, CPI films, and TAC films. Resin films may contain known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, lubricants, and anti-caking agents, as needed. There are no particular limitations on the amount of additives used; they can be set appropriately according to the intended use.

[0171] In other embodiments, a substrate comprising a porous layer is preferably used as the substrate. Examples of such porous layers include, for instance, the aforementioned foam sheets (especially open-cell foam sheets), fiber aggregates, etc. The substrate comprising the aforementioned porous layer can be a substrate containing one or more porous layers, or a substrate that, in addition to the porous layer, also has a non-porous layer (e.g., a resin membrane).

[0172] The substrate may have auxiliary layers in addition to the porous and non-porous layers described above. Examples of such auxiliary layers include decorative layers such as printing layers, primer layers, and release layers. Furthermore, conventional surface treatments such as corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, application of primer, antistatic treatment, and release treatment may be applied to the adhesive layer side surface of the substrate as needed.

[0173] The thickness of the substrate is not particularly limited. The substrate thickness can be, for example, 1 μm or more, 10 μm or more, 20 μm or more, or 30 μm or more; alternatively, it can be, for example, 5 mm or less, 2 mm or less, or 1 mm or less. In some methods where the substrate comprises a porous layer such as a foam sheet, the substrate thickness can be, for example, 50 μm or more, or 100 μm or more, 200 μm or more, or 300 μm or more. In some methods where the substrate is formed from a resin film, the substrate thickness can be, for example, 500 μm or less, or 250 μm or less, or 100 μm or less.

[0174] In the case of adhesive sheets disclosed herein having a substrate form (e.g., a substrate disposed between a first adhesive layer and a second adhesive layer), the substrate is preferably substantially insoluble in ethanol. More specifically, the weight loss rate (hereinafter also referred to as "weight loss rate caused by ethanol immersion" or simply "weight loss rate") after immersing the substrate in ethanol for 10 minutes and then drying it is preferably less than 1% by weight. Adhesive sheets with ethanol-insoluble substrates are preferred because they are less prone to adverse conditions such as dissolution or deformation of the substrate due to contact with alcoholic solvents during normal use. Furthermore, when disassembling the bond containing the adhesive sheet, it is preferable that the substrate is ethanol-insoluble from the viewpoints of reusability of the disassembled adhesive sheet and operability of separating (e.g., peeling off) the adhesive sheet from the component disassembled while it is joined with the adhesive sheet.

[0175] It should be noted that the weight loss rate of the substrate caused by ethanol impregnation was determined by the following method.

[0176] [Method for determining the weight loss rate caused by ethanol immersion] 1. Cut the substrate to be measured into 20mm×20mm sizes to make samples.

[0177] 2. Determine the initial weight (W0) of the above sample.

[0178] 3. Immerse the above sample completely in 50 mL of ethanol at 25 °C.

[0179] 4. After 10 minutes from immersion, the sample that has absorbed ethanol is removed from the ethanol. The weight (W2) of the sample after drying at 130°C for 30 minutes is determined.

[0180] 5. Calculate the weight loss rate of the substrate caused by ethanol impregnation using the following formula.

[0181] Weight reduction [%] = ((W0-W2) / W0) × 100 In some embodiments, a substrate that can absorb a certain amount of ethanol by immersion in ethanol for a short period of time is preferably used as the aforementioned substrate. Here, "substrate absorption of ethanol" includes absorption due to ethanol entering the pores of the substrate (e.g., the pores of a substrate with a porous layer) and absorption due to the swelling of the constituent materials of the substrate by ethanol. For example, the amount of ethanol absorbed (hereinafter also simply referred to as "ethanol absorption") when the substrate is immersed in ethanol for 10 minutes is preferably 25% by weight or more of the substrate weight. More specifically, the amount of ethanol absorbed by the substrate is measured by the following method.

[0182] [Method for determining ethanol absorption] 1. Cut the substrate to be measured into 20mm×20mm sizes to make samples.

[0183] 2. Determine the initial weight (W0) of the above sample.

[0184] 3. Immerse the above sample completely in 50 mL of ethanol at 25 °C.

[0185] 4. After 10 minutes from immersion, the sample that has absorbed ethanol is quietly lifted vertically from the ethanol and the weight of the sample at the time of ethanol absorption (W1) is quickly determined.

[0186] 5. Calculate the ethanol absorption of the substrate using the following formula.

[0187] Ethanol absorption [%] = ((W1-W0) / W0) × 100 For adhesive sheets with a substrate having an ethanol absorption rate of 25% by weight or more, when immersing a joint containing a component and the adhesive sheet bonded to that component in an alcohol-based release solution, the alcohol absorption of the substrate allows the release solution to be efficiently distributed throughout the joint. For example, the release solution can be efficiently introduced from the end face (outer edge) of the joint to the interior (inner side in the surface direction). Therefore, the immersion time in the release solution can be shortened in the disassembly method disclosed herein (thus shortening the time required to disassemble the joint). This reduction in immersion time by utilizing the alcohol absorption of the substrate is particularly significant when disassembling larger joints (those with a long distance from the outer edge to the center). It should be noted that in adhesive sheets with an adhesive layer forming the adhesive surface on the substrate (e.g., double-sided adhesive sheets with a substrate), the adhesive surface exhibits good alcohol-peeling properties (e.g., a peel force reduction rate R of 70% or more). A In the case of [unclear], the adhesive layer tends to exhibit improved peelability from the alcohol-absorbed substrate. Therefore, a substrate having a specified or higher ethanol absorption capacity and exhibiting a specified or higher reduction in peel force R is obtained. A For adhesive sheets (e.g., double-sided adhesive sheets with a substrate), when disassembling a joint where the adhesive surface of the adhesive sheet is bonded to a component, immersion in an alcohol-based stripping solution allows the stripping solution to act on the interface between the adhesive surface and the component, and / or the interface between the adhesive layer constituting the adhesive surface and the substrate, thereby efficiently disassembling the joint. It should be noted that in the technology disclosed herein, the disassembly of the joint in a manner where the adhesive sheet has a substrate (e.g., separation of the first component from the adhesive sheet) or alcohol stripping can be performed between the component and the adhesive layer (adhesive surface), between the substrate and the adhesive layer, or in a combination or intermediate form.

[0188] In some embodiments, the ethanol absorption of the substrate can be, for example, 50% by weight or more, 75% by weight or more, 100% by weight or more, 150% by weight or more, or 200% by weight or more. There is no particular upper limit to the ethanol absorption of the substrate. In some embodiments, from the viewpoint of suppressing excessive reduction in the strength of the substrate and suppressing the increase in the weight of the bond due to impregnation in the stripping solution, it is appropriate for the ethanol absorption of the substrate to be, for example, 2000% by weight or less, preferably 1500% by weight or less, 1000% by weight or less, or 800% by weight or less, and can be 700% by weight or less, 600% by weight or less, 500% by weight or less, or 400% by weight or less.

[0189] <Methods for Disassembling Joints> According to this specification, a method for disassembling a joint comprising an adhesive sheet having a first adhesive surface and a first component engaged with the first adhesive surface is provided. The disassembly method includes: immersing the joint in an alcohol-based peeling solution; and disassembling the joint after immersion. The peel force reduction rate R of the adhesive sheet in the aforementioned peel test is... A The success rate is over 70%. According to the above disassembly method, the aforementioned joint can be disassembled efficiently. Furthermore, by using an alcohol-based stripping liquid instead of water, even joints formed by bonding adhesive sheets to components where the peeling force reduction effect due to water peeling is not easily achieved (e.g., components with a large water contact angle on the surface) can be disassembled well. Additionally, compared to disassembly methods using water, there is a trend towards shortening or simplifying the process of removing the stripping liquid after disassembly. The adhesive sheet constituting the aforementioned joint can be, for example, any type of adhesive sheet described in this specification.

[0190] As the aforementioned alcohol-based stripping solution, a stripping solution obtained by adding a small amount of additives to an alcohol or a mixed solvent with an alcohol as the main component, as needed, can be used. As the aforementioned alcohol, a monovalent lower alcohol having 1 to 5 carbon atoms is preferred. From the viewpoints of safety and versatility, ethanol is preferred.

[0191] As a solvent other than the alcohol constituting the above-mentioned mixed solvent, water, a lower ketone (e.g., acetone), etc., that can be uniformly mixed with the alcohol can be used. As the above-mentioned additives, known surfactants, etc., can be used. From the viewpoint of avoiding contamination of the components constituting the joint, in some embodiments, a stripping solution that is substantially free of additives may be preferred.

[0192] From the viewpoint of ease of disassembly of the joint and the removability of the stripping liquid (e.g., volatile removal), in some embodiments, it is advantageous for the alcohol content in the stripping liquid to be 60% by weight or more, preferably 70% by weight or more, and can be 80% by weight or more, 90% by weight or more, 95% by weight or more, or 98% by weight or more. The alcohol content in the stripping liquid can be 100% by weight, but from the viewpoint of cost and ease of acquisition, it can be 99.9% by weight or less, 99.5% by weight or less, or 99% by weight or less, 95% by weight or less, or 90% by weight or less.

[0193] Regarding the time for immersing the joint in an alcohol-based stripping solution, it can be appropriately set in a manner that allows for suitable disassembly of the joint (preferably in a manner that avoids damage or deformation of the components). From the viewpoint of shortening the time required for disassembly (the time from the start of immersion in the stripping solution until the separation of at least one component is completed), in some embodiments, it is appropriate to set the immersion time of the joint in the stripping solution to 3 hours or less, preferably 1 hour or less, more preferably 30 minutes or less, and also 20 minutes or less or 15 minutes or less. In other embodiments, the immersion time can be, for example, 30 seconds or more, 1 minute or more, 3 minutes or more, or 5 minutes or more. A suitable immersion time may vary depending on the shape and size (joint area) of the joint. Regarding the immersion time, it can be appropriately applied, for example, as the immersion time for disassembling a joint constructed by joining a flat first component and a flat second component using a 100mm × 50mm adhesive sheet (without a substrate or with a substrate double-sided adhesive sheet).

[0194] The impregnation of the joint in the aforementioned stripping solution can be carried out at room temperature (around 15°C to 30°C, for example, around 25°C), or at temperatures higher or lower than room temperature. From the viewpoint of maximizing the effect of impregnation, impregnation at temperatures higher than room temperature is advantageous. From the viewpoint of avoiding excessive evaporation of the stripping solution, in some methods, setting the aforementioned temperature above room temperature to, for example, below 60°C is appropriate, and it can also be set to below 50°C or below 40°C.

[0195] After the joint is immersed in the stripping liquid, the operation of disassembling the joint (which can be understood as the operation of separating at least a portion of the constituent elements of the joint from the other parts) can be performed after removal from the stripping liquid or while in the stripping liquid. From the viewpoint of operability during the disassembly operation and to suppress contamination of the stripping liquid, in some embodiments, it is preferable to perform the disassembly operation after removing the joint from the stripping liquid. It should be noted that in the disassembly method disclosed herein, it is acceptable for the joint to disassemble naturally (without external force) during immersion in the stripping liquid; however, in some embodiments, from the viewpoint of managing the timing of disassembly, it is preferable to apply external force to the joint after immersion in the stripping liquid (after removal from the stripping liquid) to perform the disassembly operation.

[0196] In some methods, disassembly of the bond after immersion in a release solution may include separating the first adhesive layer constituting the first adhesive surface from the component adjacent to the first adhesive layer. The component adjacent to the first adhesive layer may be a component (the adhered object) that is bonded to the first adhesive surface of the adhesive sheet before disassembly, or it may be a component adjacent to the back side of the first adhesive layer (the surface opposite to the first adhesive surface). The component adjacent to the back side of the first adhesive layer may be, for example, the second component in a bond obtained by bonding a first component and a second component through the first adhesive layer (a substrate-free double-sided adhesive sheet), or it may be the substrate in a substrate-bearing adhesive sheet. Therefore, when disassembling a substrate-bonded adhesive sheet containing a first adhesive layer on a substrate using the disassembly method disclosed herein, the disassembly of the adhesive sheet after immersion in the stripping liquid can be carried out in a manner in which the first component and the first adhesive layer are separated first, or in a manner in which the first adhesive layer and the component adjacent to its back side (e.g., the second component or the substrate of the adhesive sheet) are separated first, or in a manner in which they are combined or intermediate. Furthermore, when disassembling the aforementioned adhesive sheet with a substrate, which is a double-sided adhesive sheet with a substrate, and in which the first adhesive surface of the double-sided adhesive sheet with a substrate is bonded to the first component and the second adhesive surface is bonded to the second component, the disassembly of the joint after immersion in the peeling liquid can be performed by separating the first component and the first adhesive layer first, or by separating the first adhesive layer and the substrate adjacent to its back side first, or by separating the second component and the second adhesive layer first, or by separating the second adhesive layer and the substrate adjacent to its back side first, or by combining or interleaving these methods. According to the technology disclosed herein, by reducing the peel force by the aforementioned rate R... A With a peeling force reduction rate of 70% or higher, any of the above methods can achieve the effect of facilitating the disintegration of the joint by immersion in the peeling liquid. Furthermore, by reducing the peeling force R... A With a separation rate of over 70%, even if the initial separation after immersion in the stripping solution is carried out at a location other than the interface between the first component and the first adhesive layer, the first component and the first adhesive layer can be easily separated at a suitable time thereafter.

[0197] When a bond being disassembled using the disassembly method disclosed herein comprises an adhesive sheet having a substrate shape (e.g., a substrate shape disposed between a first adhesive layer and a second adhesive layer), the substrate is preferably one that can absorb a certain amount of release liquid by being immersed in the release liquid (e.g., ethanol) used in the disassembly method for a short time. Thus, for example, when the bond comprising the component and the adhesive sheet joined to the component is immersed in the release liquid, the release liquid absorbency of the substrate allows the release liquid to be efficiently distributed throughout the joint. For example, the release liquid can be efficiently introduced from the end face (outer edge) of the bond to the interior (inner side in the surface direction). Therefore, the immersion time in the release liquid can be shortened in the disassembly method disclosed herein (thereby shortening the time required to disassemble the bond). In some embodiments, the amount of release liquid absorbed (hereinafter also referred to as "release liquid absorption") when the substrate is immersed in the release liquid for 10 minutes is preferably, for example, 25% by weight or more of the substrate. Regarding the amount of release fluid absorbed by the substrate, the measurement is performed in the same manner as the method for measuring the amount of ethanol absorption described above, except that the release fluid (which may also be ethanol) used in the disassembly of the aforementioned bond is used instead of ethanol. As the upper limit of the amount of release fluid absorbed by the substrate, any of the upper limit values ​​exemplified in the description of the amount of ethanol absorption described above may be used. Similarly, as the lower limit of the amount of release fluid absorbed by the substrate, any of the lower limit values ​​exemplified in the description of the amount of ethanol absorption described above may be used.

[0198] In some of the disassembly methods disclosed herein, the substrate contained in the bond being disassembled using this disassembly method is preferably substantially insoluble in the stripping liquid (e.g., ethanol) used in the disassembly method. For example, the weight loss rate (hereinafter also referred to as "weight loss rate caused by stripping liquid immersion") of the substrate after immersion in the stripping liquid for 10 minutes and then drying it is preferably less than 1% by weight. This is advantageous from the viewpoints of reusability of the disassembled adhesive sheet and operability when separating (e.g., peeling off) the adhesive sheet from the component disassembled while it is in the bonded state. Regarding the weight loss rate of the substrate caused by stripping liquid immersion, the measurement is performed in the same manner as the method for measuring the weight loss rate caused by ethanol immersion described above, except that the stripping liquid (which may also be ethanol) used in the disassembly of the bond can be used instead of ethanol. As an upper limit for the weight loss rate of the substrate caused by stripping liquid immersion, any of the upper limit values ​​exemplified in the description of the weight loss rate caused by ethanol immersion described above can be used. Similarly, the lower limit of the weight reduction rate caused by impregnation with the stripping solution for the substrate can be any of the lower limit values ​​exemplified in the description of the weight reduction rate caused by impregnation with ethanol described above.

[0199] <Uses> The adhesive sheet disclosed herein can flexibly utilize the advantages of both reliable bonding and alcohol-based peelability (and, consequently, ease of disassembly based on alcohol-based peeling liquid) for applications such as fixing, joining, molding, decorating, protecting, and supporting components in various portable devices, automobiles, and home appliances. As for the material constituting at least the surface of the aforementioned component, the same material as that constituting at least the surface of the first or second component described above can be used as an example.

[0200] As an example of a preferred application, optical applications can be cited. The technology disclosed herein can be preferably implemented as an optical adhesive sheet used in applications such as bonding optical components (for bonding optical components), manufacturing articles using the aforementioned optical components (optical articles), and disassembly methods for joints containing such adhesive sheets.

[0201] The aforementioned optical components refer to components possessing optical properties (e.g., polarization, refraction, scattering, reflection, transmission, absorption, diffraction, rotation, visual recognition, etc.). There is no particular limitation on the term "optical component" as long as it possesses optical properties. Examples include components constituting display devices (image display devices), input devices, and other equipment (optical devices), or components used in these devices. Examples include polarizing plates, wavelength plates, phase retardation plates, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflective films, hard coating (HC) films, impact absorption films, anti-fouling films, photochromic films, dimming films, transparent conductive films (ITO films), design films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates, and components in which they are stacked (sometimes collectively referred to as "functional films"). It should be noted that the terms "plate" and "film" mentioned above each include plate-like, film-like, and sheet-like forms. For example, "polarizing film" includes "polarizing plate" and "polarizing sheet".

[0202] Examples of display devices include liquid crystal displays, organic EL displays, PDPs, and electronic paper. The technologies disclosed herein are particularly suitable for applications involving high-cost components, such as foldable displays and automotive displays. Furthermore, the aforementioned display devices include input-enabled display devices such as touch panels. Given the strong demand for recycling and reuse of these display devices, the application of the technologies disclosed herein is especially meaningful.

[0203] The optical components described above are not particularly limited, and examples include components formed from glass, acrylic resin, polycarbonate, polyethylene terephthalate, metal films, etc. (e.g., sheet-like, film-like, plate-like components). It should be noted that the term "optical component" in this specification may include components that serve a decorative or protective function while maintaining the visual legibility of the display device or input device (design films, decorative films, surface protective films, etc.).

[0204] Examples of other applications of the connector disclosed herein, including articles, devices, and structures incorporating the connector, include applications such as fixing protective panels (lenses) for display sections of electronic devices, fixing decorative panels for displays (e.g., television displays), fixing batteries for electronic devices, and fixing circuit boards (glass core substrates, organic resin substrates, etc.) for integrated circuit (IC) devices in electronic devices. For example, it can be suitable for electronic devices (preferably portable electronic devices) where high bonding reliability based on adhesive sheets is required during component bonding, and where smooth removal is required during component repair, replacement, inspection, and recycling. For example, it can be appropriately used in mobile phones, smartphones, tablets, laptops, various wearable devices (e.g., wrist-worn types like watches, modular types worn on the body with clips, straps, etc., including eyeglass types (monocular, binocular, and headband types), types attached to clothing such as shirts, socks, and hats as accessories, and ear-worn types like headphones), digital cameras, digital camcorders, audio equipment (portable music players, IC recorders, etc.), calculators (electronic calculators, etc.), mobile gaming devices, etc. This invention relates to portable electronic devices such as electronic dictionaries, electronic notebooks, e-books, in-vehicle information devices, mobile radios, mobile TVs, mobile printers, mobile scanners, and mobile modems. It covers the fixing of protective panels (lenses) for the display unit, key module components, wheel rims, decorative panels, batteries, circuit boards, and various other components (various panel components, buttons, lighting components, internal camera components, heat dissipation materials, graphite sheets), as well as logos (fancy text) and various design markings (including various badges). Furthermore, the aforementioned display devices can be components of electronic devices such as desktop computers, monitors, and televisions (LCD, plasma, OLED, etc.). It should be noted that the term "portable (or mobile)" in this specification refers not only to the ability to carry but also to a level of portability that allows a standard adult to move the device relatively easily.

[0205] The matters disclosed in this specification include the following.

[0206] [1] A disassembly method, comprising disassembling an adhesive sheet having a first adhesive surface and a first component engaged with said first adhesive surface, wherein the disassembly method includes: The above-mentioned conjugate was immersed in a stripping solution mainly composed of lower alcohols having 1 to 5 carbon atoms; and After the above impregnation, the above-mentioned joint is disassembled. In the peel test described below, the reduction rate R of the ethanol peel force N1 [N / 20mm] relative to the normal peel force N0 [N / 20mm] at the first measurement of the above adhesive sheet is... A The percentage is over 70%, and the average peel force N0 in the second measurement is relative to the average peel force N0 [N / 20mm] in the first measurement. S [N / 20mm] reduction rate R B It is below 30%.

[0207] [Peeling Test] (First measurement) The first adhesive surface of the adhesive sheet was adhered to a stainless steel plate and placed in an autoclave. The plate was then treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After removal from the autoclave, the plate was allowed to stand for 30 minutes at 23°C and 50% RH. Under the same conditions, the adhesive sheet was then peeled from the stainless steel plate using a tensile testing machine at a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol was added dropwise to the point where the adhesive sheet began to separate from the stainless steel plate. The peel strength observed before the addition of ethanol was designated as the normal peel force N0 [N / 20 mm], and the peel strength observed after the addition of ethanol was designated as the ethanol peel force N1 [N / 20 mm]. (Second measurement) After drying the adhesive sheet used in the first test, the first adhesive surface of the adhesive sheet was adhered to a new stainless steel plate. The plate was then placed in an autoclave and treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After being removed from the autoclave and allowed to stand for 30 minutes at 23°C and 50% RH, the adhesive sheet was peeled from the stainless steel plate using a tensile testing machine under the same conditions, with a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol was added dropwise to the point where the adhesive sheet began to separate from the stainless steel plate. The peel strength observed before the addition of ethanol was designated as the normal peel force N0. S [N / 20mm], the peel strength observed after ethanol addition will be defined as the ethanol peel force N1. S [N / 20mm].

[0208] [2] The disassembly method described in [1] above, wherein the contact angle of the first component with distilled water is 50 degrees or more.

[0209] [3] The disassembly method as described in [1] or [2] above, wherein the first adhesive surface is the surface of an acrylic adhesive layer containing an acrylic polymer as the base polymer.

[0210] [4] The disintegration method as described in [3] above, wherein the monomer component constituting the acrylic polymer comprises an alkyl (meth) acrylate having an alkyl group having 10 to 14 carbon atoms.

[0211] [5] The disassembly method as described in [1] or [2] above, wherein the first adhesive surface is the surface of a polyester adhesive layer containing a polyester polymer as the base polymer.

[0212] [6] The disassembly method as described in any one of [1] to [5] above, wherein the adhesive sheet is a double-sided adhesive sheet with the surface opposite to the first adhesive surface as the second adhesive surface. The aforementioned joint also includes a second component that is bonded to the aforementioned second adhesive surface.

[0213] [7] An adhesive sheet having: The first adhesive layer constituting the first adhesive surface; A second adhesive layer constituting the second adhesive surface, wherein the second adhesive surface is the surface opposite to the first adhesive surface; and A substrate disposed between the first adhesive layer and the second adhesive layer. In the case where the substrate is immersed in ethanol for 10 minutes and then dried, the weight loss rate of the substrate is less than 1% by weight. In the peel test described below, the reduction rate R of the ethanol peel force N1 [N / 20mm] of the above-mentioned adhesive sheet relative to the normal peel force N0 [N / 20mm] is measured. A It is over 70%. [Peeling Test] The first adhesive side of the adhesive sheet was attached to a stainless steel plate and placed in an autoclave. It was then treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After being removed from the autoclave, the adhesive sheet was allowed to stand for 30 minutes at 23°C and 50%RH. Then, it was peeled from the stainless steel plate using a tensile testing machine under the same conditions, with a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol was added to the part of the adhesive sheet that began to separate from the stainless steel plate. The peel strength observed before the addition of ethanol was defined as the normal peel strength N0 [N / 20 mm], and the peel strength observed after the addition of ethanol was defined as the ethanol peel strength N1 [N / 20 mm].

[0214] [8] The adhesive sheet as described in [7] above, wherein the amount of ethanol absorbed when the substrate is immersed in ethanol for 10 minutes is 25% by weight or more of the weight of the substrate.

[0215] [9] The adhesive sheet as described in [7] or [8] above, wherein the first adhesive layer is an acrylic adhesive layer containing an acrylic polymer as the base polymer.

[0216]

[10] The adhesive sheet as described in [9] above, wherein the monomer component constituting the acrylic polymer comprises an alkyl (meth)acrylate having an alkyl group having 10 to 14 carbon atoms.

[0217]

[11] The adhesive sheet as described in

[10] above, wherein the monomer component constituting the acrylic polymer further includes an alkyl (meth)acrylate having an alkyl group having 4 to 9 carbon atoms.

[0218]

[12] The adhesive sheet as described in any one of [9] to

[11] above, wherein the acrylic adhesive layer further comprises an acrylic oligomer.

[0219]

[13] The adhesive sheet as described in [7] or [8] above, wherein the first adhesive layer is a polyester adhesive layer containing a polyester polymer as the base polymer.

[0220] Example The following describes some embodiments related to the present invention, but it is not intended to limit the invention to the contents shown in these embodiments. It should be noted that, unless otherwise stated, in the following description, "parts" and "%" are based on weight.

[0221] <Preparation of Adhesive Compositions> (Adhesive composition A1) A monomer mixture comprising 2-ethylhexyl acrylate (2EHA), lauryl acrylate (LA), and photopolymerization initiator A (trade name "Omnirad 184", manufactured by IGM Resins) in a weight ratio of 70 / 30 / 0.1 was added to a four-necked flask and subjected to photopolymerization under a nitrogen atmosphere by irradiation with ultraviolet light until the viscosity (BH viscometer, No. 5 rotor, 10 rpm, measurement temperature 30°C. Unless otherwise specified, the same applies below) reached approximately 15 Pa·s, thereby preparing a monomer slurry S1 containing a portion of the polymer from the above monomer mixture. 0.1 parts of 1,6-hexanediol diacrylate (HDDA) was added to 100 parts of this monomer slurry S1 as a crosslinking agent, and the mixture was uniformly mixed to prepare an adhesive composition A1.

[0222] (Adhesive composition A2) Using a monomer mixture comprising 2EHA, LA, N-vinyl-2-pyrrolidone (NVP), and photopolymerization initiator A in a weight ratio of 70 / 30 / 10 / 0.1, a monomer slurry S2 comprising a portion of the polymer from the monomer mixture is prepared in the same manner as the preparation of monomer slurry S1 described above. 0.1 parts of HDDA are added to 100 parts of monomer slurry S2, and the mixture is homogeneously mixed to prepare adhesive composition A2.

[0223] (Adhesive composition A3) Add 0.1 parts of HDDA and 2 parts of acrylic oligomer A to 100 parts of the above monomer slurry S2, and mix evenly to prepare adhesive composition A3.

[0224] As acrylic oligomer A, the substance synthesized by the following method is used.

[0225] Synthesis of acrylic oligomer A 100 parts of toluene, 60 parts of dicyclopentyl methacrylate (DCPMA) (trade name "FA-513M", manufactured by Hitachi Chemical Co., Ltd.), 40 parts of methyl methacrylate (MMA), and 3.5 parts of α-thioglycerol as a chain transfer agent were added to a four-necked flask. The mixture was stirred at 70°C under a nitrogen atmosphere for 1 hour. Then, 0.2 parts of 2,2'-azobisisobutyronitrile (2,2'-Azobisisobutyronitrile) were added as a thermal polymerization initiator, and the reaction was carried out at 70°C for 2 hours, followed by a reaction at 80°C for 2 hours. The reaction solution was then dried at 130°C to remove toluene, chain transfer agent, and unreacted monomers, thus obtaining a solid acrylic oligomer A. The Tg of acrylic oligomer A was 144°C, and the Mw was 4300.

[0226] (Adhesive composition A4) Using a monomer mixture comprising n-butyl acrylate (BA), LA, and photopolymerization initiator A in a weight ratio of 70 / 30 / 0.1, a monomer slurry S4 comprising a portion of the polymer from the monomer mixture is prepared in the same manner as the preparation of monomer slurry S1. 0.1 parts of HDDA and 2 parts of the aforementioned acrylic oligomer A are added to 100 parts of monomer slurry S4, and the mixture is homogeneously mixed to prepare adhesive composition A4.

[0227] (Adhesive composition A5) Using a monomer mixture comprising 2EHA, LA, and photopolymerization initiator A in a 50 / 50 / 0.1 weight ratio, a monomer slurry S5 comprising a portion of the polymer from the monomer mixture is prepared in the same manner as the preparation of monomer slurry S1 described above. 0.1 parts of HDDA are added to 100 parts of monomer slurry S5, and the mixture is homogeneously mixed to prepare adhesive composition A5.

[0228] (Adhesive composition A6) Using a monomer mixture comprising 2EHA, LA, 4-hydroxybutyl acrylate (4HBA), and photopolymerization initiator A in a weight ratio of 70 / 30 / 10 / 0.1, a monomer slurry S6 comprising a portion of the polymer from the monomer mixture is prepared in the same manner as the monomer slurry S1 described above. 0.1 parts of HDDA are added to 100 parts of this monomer slurry S6, and the mixture is homogeneously mixed to prepare adhesive composition A6.

[0229] (Adhesive composition A7) Using a monomer mixture comprising BA, 4HBA, cyclohexyl acrylate (CHA), and photopolymerization initiator A in a weight ratio of 80 / 20 / 20 / 0.1, a monomer slurry S7 comprising a portion of the polymer from the monomer mixture is prepared in the same manner as the preparation of monomer slurry S1. 0.1 parts of HDDA are added to 100 parts of monomer slurry S7, and the mixture is homogeneously mixed to prepare adhesive composition A7.

[0230] (Adhesive composition E1) For a commercially available polyester polymer (grade name "SNT", manufactured by Mitsubishi Chemical Co., Ltd., Tg: -15℃, hydroxyl value: 6~10mgKOH / g, acid value: <1mgKOH / g), based on solid component basis, add 3 parts of isocyanate-based crosslinking agent (TDI-based polyisocyanate available from Mitsui Chemicals Co., Ltd., shown as "isocyanate A" in Table 2) to 100 parts of the above polymer, 0.01 parts of organotin compound as crosslinking catalyst (trade name "dibutyltin dilaurate (IV)", manufactured by Fujifilm and Koko Pure Chemical Co., Ltd., hereinafter referred to as "DBTDL"), and 1 part of carbodiimide-containing compound as hydrolysis resistant agent (trade name "CARBODILITE V-07", manufactured by Nisshinbo Chemical Co., Ltd.), and mix them evenly to prepare adhesive composition E1.

[0231] (Adhesive composition E2) For a commercially available polyester polymer (grade name "NP-111S50EO", manufactured by Mitsubishi Chemical Co., Ltd., Tg: -48℃, hydroxyl value: 2~8mgKOH / g, acid value: <1mgKOH / g), based on solid component basis, add 1 part of isocyanate-based crosslinking agent (trade name "CORONATE HX", manufactured by Tosoh Co., Ltd., HDI isocyanurate-based polyisocyanate. Shown as "isocyanate B" in Table 2) to 100 parts of the above polymer, 0.01 parts of DBTDL as a crosslinking catalyst, and 1 part of a carbodiimide-containing compound (trade name "CARBODILITE V-07", manufactured by Nisshinbo Chemical Co., Ltd.) as a hydrolysis resistant agent, and mix them evenly to prepare adhesive composition E2.

[0232] (Adhesive composition E3) Without using a hydrolysis-resistant agent and a crosslinking catalyst, the crosslinking agent was changed from isocyanate B to isocyanate A. Otherwise, the same procedure was followed as in the preparation of adhesive composition E2 to prepare adhesive composition E3.

[0233] <Making Adhesive Sheets> (Example 1) Adhesive composition A1 was coated onto a 38 μm thick polyethylene terephthalate (PET) film R1, which had been silicone-treated on one side. A 38 μm thick PET film R2, also silicone-treated on one side, was then placed over the film to block air. The film was then cured by ultraviolet light, forming an adhesive layer with a thickness of 25 μm. The ultraviolet light irradiation was performed using a black light at an illuminance of 2.5 mW / cm². 2 (Measured using an industrial UV inspector (TOPCON, trade name "UVR-T1") with a peak sensitivity wavelength of approximately 350 nm) and irradiated for 960 seconds. Thus, the adhesive sheet (a substrate-free double-sided adhesive sheet formed from the adhesive layer) according to Example 1 was obtained with the first and second adhesive surfaces protected by the aforementioned release films R1 and R2.

[0234] (Examples 2-6, Comparative Example 1) Instead of adhesive composition A1, adhesive compositions A2 to A7 are used. Otherwise, the same procedure is followed as in the production of the adhesive sheet in Example 1, and the adhesive sheets (substrate-free double-sided adhesive sheets formed from the adhesive layer) are obtained in such a way that the first and second adhesive surfaces are protected by the release films R1 and R2.

[0235] (Comparative Example 2) A mixture of 100 parts of polyamide (trade name "Platamid M1276", manufactured by Arkema, a polyamide with a piperazine backbone, weight average molecular weight 21,000) and 0.5 parts of epoxy crosslinking agent (trade name "TETRAD-C", manufactured by Mitsubishi Gas Chemical Co., Ltd.) was applied to a resin sheet (release sheet: CA1 manufactured by FUJICO CO.,LTD.) with a surface that had undergone a release treatment using a coater. The sheet was then placed in a constant temperature dryer and dried at 100°C for 5 minutes to produce the polyamide adhesive sheet (thickness 25 μm) involved in Comparative Example 2.

[0236] (Example 7) Adhesive composition E1 was applied to the release side of a PET film R3 (75 μm thick) that had been treated with silicone on one side, and dried at 110°C for 2 minutes to form an adhesive layer with a thickness of 30 μm. The release side of release film R2 was then adhered to the adhesive layer on release film R3. By doing so, the adhesive sheet (a substrate-free double-sided adhesive sheet formed from the adhesive layer) according to Example 7 was obtained with the first and second adhesive sides protected by the release films R3 and R2.

[0237] (Examples 8 and 9) In addition to using adhesive compositions E2 and E3 instead of adhesive composition E1, the adhesive sheet was prepared in the same manner as that described in Example 7, and the adhesive sheet (a substrate-free double-sided adhesive sheet formed from the adhesive layer) was obtained with the first and second adhesive surfaces protected by the release films R3 and R2.

[0238] (Example 10) The adhesive layer of Example 2 is adhered to the first and second sides of a polyurethane foam sheet A1 (1000 μm thick, trade name "RUBYLAR L03", manufactured by TOYOPOLYMER, abbreviated as "urethane A1" in Table 3) as a substrate, thereby producing an adhesive sheet (double-sided adhesive sheet with substrate) having the structure of adhesive layer / polyurethane foam sheet A1 / adhesive layer.

[0239] (Example 11) As the substrate, a polyurethane foam sheet A2 (400 μm thick, trade name "RUBYLAR L03", manufactured by TOYOPOLYMER, abbreviated as "urethane A2" in Table 3) was used. Otherwise, the adhesive sheet (double-sided adhesive sheet with substrate) involved in this example was produced in the same manner as the adhesive sheet involved in Example 10.

[0240] (Example 12) As the substrate, polyurethane foam sheet B (1000 μm thick, trade name "RUBYLAR L31", manufactured by TOYOPOLYMER, abbreviated as "urethane B" in Table 2) was used. Otherwise, the adhesive sheet (double-sided adhesive sheet with substrate) involved in this example was produced in the same manner as the adhesive sheet involved in Example 10.

[0241] (Example 13) The nonwoven fabric (a polyester nonwoven fabric with a thickness of 1000 μm) was used as the substrate. Otherwise, the adhesive sheet (a double-sided adhesive sheet with a substrate) involved in this example was produced in the same manner as the adhesive sheet involved in Example 10.

[0242] (Example 14) The adhesive layer of Example 7 is adhered to the first and second sides of a polyurethane sheet C (30 μm thick, manufactured by Sheedom, abbreviated as "urethane C" in Table 3) as a substrate, thereby producing an adhesive sheet (double-sided adhesive sheet with substrate) having the structure of adhesive layer / polyurethane sheet C / adhesive layer.

[0243] It should be noted that, for each substrate used in Examples 10 to 14, the results of measuring the ethanol absorption [%] and the weight loss rate [%] caused by ethanol impregnation using the above method are shown in Table 3.

[0244] <Measurement and Evaluation> (1) Peel test (Typically, the peel force is N0) A 50 μm thick PET film was adhered to the second adhesive surface of the adhesive sheet to be tested, and then cut into rectangular shapes with a width of 20 mm and a length of 120 mm to prepare test pieces. The first adhesive surface of the test piece was adhered to a stainless steel plate (SUS430BA plate) as the substrate using a hand roller. The resulting evaluation sample was placed in an autoclave and treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After being removed from the autoclave and allowed to stand for 30 minutes at 23°C and 50% RH, the evaluation sample was peeled from the stainless steel plate using a tensile testing machine (Minebea, universal tensile and compression testing machine, TCM-1kNB) under the same conditions, at a tensile speed of 300 mm / min and a peel angle of 180 degrees. The peel strength was measured. Three tests were performed, and their average value was taken as the typical peel force N0 in the first test, as shown in Tables 1-3.

[0245] (Ethanol peeling force N1) In the above-mentioned general peel strength N0 determination, during the peeling of the adhesive sheet from the stainless steel plate, 20 μL of ethanol was supplied to the part of the test piece that began to separate from the stainless steel plate (peeling interface), and the peel strength after the ethanol supply was measured. Each peel strength N0 was measured (i.e., 3 times), and their average value was taken as the ethanol peel strength N1 in the first measurement, as shown in Tables 1 to 3.

[0246] (Typically, peel force N0) S ) The test pieces used in the above-mentioned tests of normal peel strength N0 and ethanol peel strength N1 were dried at 23°C for 60 minutes to allow the ethanol adhering during the ethanol peel strength N1 test to evaporate. Then, the first adhesive surface of the test piece was adhered to a new stainless steel plate (SUS430BA plate) as the substrate using a hand roller. The resulting evaluation sample was placed in an autoclave and treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After being removed from the autoclave and allowed to stand for 30 minutes at 23°C and 50% RH, the evaluation sample was peeled from the stainless steel plate using a tensile testing machine (Minebea, universal tensile and compression testing machine, TCM-1kNB) under the same conditions, at a tensile speed of 300 mm / min and a peel angle of 180 degrees. The peel strength was measured. The test was performed three times, and the average value was taken as the normal peel strength N0 in the second test. S As shown in Tables 1-3.

[0247] (Ethanol peeling force N1) S ) The above-mentioned typical peel force N0 S In the test, during the peeling of the adhesive sheet from the stainless steel plate, 20 μL of ethanol was supplied to the part of the test piece where it began to separate from the stainless steel plate (peeling interface), and the peel strength after the ethanol supply was measured. Each peel strength N0 was measured three times, and their average value was taken as the ethanol peel force N1 in the second measurement. S As shown in Tables 1-3.

[0248] Based on the measured values, the peel force reduction rate R is calculated using the above formula. A Peel force reduction rate R AS and typical peel strength reduction rate R B .

[0249] (2) Disintegration of the joint The double-sided adhesive sheets involved in each example were cut to a size of 100mm × 50mm. The release liner was peeled off to expose the first adhesive surface. The exposed first adhesive surface was then adhered to a stainless steel plate (SUS430BA plate, size 100mm × 50mm, thickness 0.5mm) serving as the first component. The release liner was then peeled off to expose the second adhesive surface. The exposed second adhesive surface was then adhered to an alkali glass plate (Matsunami Glass Industry Co., Ltd., size 165mm × 65mm, thickness 1.35mm, blue-edged polished) serving as the second component. The resulting articles were placed in an autoclave and treated at 50°C and 5 atmospheres for 15 minutes (autoclave treatment). After being removed from the autoclave, they were allowed to stand at room temperature and pressure (23°C, 1 atmosphere) for 30 minutes. This process yielded a laminated structure formed from a stainless steel plate / adhesive layer / alkali glass plate, which was used as an evaluation sample. In the samples used for evaluation, stainless steel plates and alkali glass plates were joined together with an adhesive layer at a bonding area of ​​100mm × 50mm. It should be noted that the tensile modulus of the aforementioned alkali glass plate is 7 × 10⁻⁶. 10 Pa, bending stiffness is approximately 14 Pa·m 3 (Poisson's ratio 0.23).

[0250] At room temperature (approximately 25°C), add ethanol (peeling solution) to a container until the depth is approximately 2 cm, immersing the aforementioned joint in the ethanol. After 10 minutes, remove the joint from the ethanol and attempt to disassemble it by hand (an adult female, with all evaluations performed by the same person). Specifically, insert a ruler (or metal plate) into the interlayer portion at the end of the evaluation sample, penetrating approximately 10 mm, and apply force in the vertical direction (the thickness direction of the evaluation sample) to attempt disassembly. A joint that can be disassembled is evaluated as "acceptable," while a joint that cannot be disassembled is evaluated as "unacceptable."

[0251] [Table 1] [Table 2] [Table 3] As shown in Tables 1-3, the peel force reduction rate R is used. A The joints constructed from the adhesive sheets of Examples 1-14, accounting for over 70% of the total, could be efficiently disintegrated by immersion in ethanol (peeling solution) for a short period of 10 minutes. On the other hand, using the peel force reduction rate R... AThe bond constructed from the adhesive sheet in Comparative Example 1 could not be disassembled under the aforementioned immersion conditions. Furthermore, in Comparative Example 2, although the bond could be disassembled under the aforementioned immersion conditions due to the dissolution of the polyamide adhesive in the release solution, the peel force measured after the addition of ethanol became significantly unstable in the first peel test, making it impossible to obtain meaningful test results. Additionally, the adhesiveness was essentially lost from the test piece that was peeled off after the first test, making a second test impossible.

[0252] The specific examples of the present invention have been described in detail above, but the above description is merely illustrative and does not limit the scope of the claims. The technology described in the claims includes solutions obtained by various modifications and alterations to the specific examples described above.

[0253] Explanation of reference numerals in the attached figures 1, 2 adhesive sheets 11 First adhesive layer 11a First adhesive surface 12 Second adhesive layer 12a Second adhesive surface 20 Substrate 20a Side 1 20b Page 2 31, 32 Peeling off the gasket 50 Adhesive sheets with release liner 61 Part 1 62 Part 2 100, 200 joint

Claims

1. A disassembly method comprising disassembling an adhesive sheet having a first adhesive surface and a first component engaged with said first adhesive surface, wherein, The dismantling method includes: The conjugate is immersed in a stripping solution primarily composed of lower alcohols having 1 to 5 carbon atoms; and The joint is disassembled after the impregnation. In the peel test described below, the reduction rate R of the ethanol peel force N1 [N / 20mm] relative to the normal peel force N0 [N / 20mm] at the first measurement of the adhesive sheet is... A The percentage is over 70%, and the average peel force N0 in the second measurement is relative to the average peel force N0 [N / 20mm] in the first measurement. S [N / 20mm] reduction rate R B Below 30%, [Peeling Test] (First measurement) The first adhesive surface of the adhesive sheet is adhered to a stainless steel plate, placed in an autoclave, and treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After being removed from the autoclave and left to stand for 30 minutes at 23°C and 50%RH, the adhesive sheet is peeled from the stainless steel plate using a tensile testing machine under the same conditions at a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol is added to the part of the adhesive sheet that begins to separate from the stainless steel plate. The peel strength observed before the addition of ethanol is set as the normal peel force N0 [N / 20 mm], and the peel strength observed after the addition of ethanol is set as the ethanol peel force N1 [N / 20 mm]. (Second measurement) After drying the adhesive sheet used in the first test, the first adhesive surface of the adhesive sheet was adhered to a new stainless steel plate. The plate was then placed in an autoclave and treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After being removed from the autoclave and allowed to stand for 30 minutes at 23°C and 50% RH, the adhesive sheet was peeled from the stainless steel plate using a tensile testing machine under the same conditions, with a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol was added dropwise to the point where the adhesive sheet began to separate from the stainless steel plate. The peel strength observed before the addition of ethanol was designated as the normal peel force N0. S [N / 20mm], the peel strength observed after ethanol addition will be defined as the ethanol peel force N1. S [N / 20mm].

2. The dismantling method as described in claim 1, wherein, The contact angle of the first component with distilled water is greater than 50 degrees.

3. The dismantling method as described in claim 1 or 2, wherein, The first adhesive surface is the surface of an acrylic adhesive layer containing an acrylic polymer as the base polymer.

4. The dismantling method as described in claim 3, wherein, The monomer components constituting the acrylic polymer include alkyl (meth)acrylates having alkyl groups having 10 to 14 carbon atoms.

5. The dismantling method as described in claim 1 or 2, wherein, The first adhesive surface is the surface of a polyester adhesive layer containing a polyester polymer as the base polymer.

6. The dismantling method as described in claim 1 or 2, wherein, The adhesive sheet is a double-sided adhesive sheet in which the surface opposite to the first adhesive surface becomes the second adhesive surface. The joint further includes a second component that engages with the second adhesive surface.

7. An adhesive sheet comprising: The first adhesive layer constituting the first adhesive surface; A second adhesive layer constituting the second adhesive surface, said second adhesive surface being the surface opposite to the first adhesive surface; and A substrate disposed between the first adhesive layer and the second adhesive layer. in, When the substrate is immersed in ethanol for 10 minutes and then dried, the weight loss rate of the substrate is less than 1% by weight. In the peel test described below, the reduction rate R of the ethanol peel force N1 [N / 20mm] of the adhesive sheet relative to the usual peel force N0 [N / 20mm] is measured. A It is over 70%. [Peeling Test] The first adhesive surface of the adhesive sheet is attached to a stainless steel plate and placed in an autoclave. It is then treated for 15 minutes at a pressure of 5 atm and a temperature of 50°C. After being removed from the autoclave, the adhesive sheet is allowed to stand for 30 minutes at 23°C and 50%RH. Under the same conditions, the adhesive sheet is peeled off from the stainless steel plate using a tensile testing machine at a peel angle of 180 degrees and a tensile speed of 300 mm / min. During the peeling process, 20 μL of ethanol is added to the part of the adhesive sheet that begins to separate from the stainless steel plate. The peel strength observed before the addition of ethanol is set as the normal peel force N0 [N / 20 mm], and the peel strength observed after the addition of ethanol is set as the ethanol peel force N1 [N / 20 mm].

8. The adhesive sheet as claimed in claim 7, wherein, When the substrate is immersed in ethanol for 10 minutes, the amount of ethanol absorbed is more than 25% by weight of the substrate.

9. The adhesive sheet as claimed in claim 7 or 8, wherein, The first adhesive layer is an acrylic adhesive layer containing an acrylic polymer as the base polymer.

10. The adhesive sheet as claimed in claim 9, wherein, The monomer components constituting the acrylic polymer include alkyl (meth)acrylates having alkyl groups having 10 to 14 carbon atoms.

11. The adhesive sheet as claimed in claim 7 or 8, wherein, The first adhesive layer is a polyester adhesive layer containing a polyester polymer as the base polymer.

Citation Information

Patent Citations

  • Adhesive sheet and method for peeling adhesive sheet

    JP2020023656A

  • Adhesive sheet and use thereof

    JP2021138934A

  • Bonded object separation method

    WO2022038926A1